Acrylic rubber veil with excellent workability and water resistance

JP7610358B2Active Publication Date: 2025-01-08ZEON CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020098308
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-19
Filing Date
2020-06-05
Publication Date
2025-01-08
Estimated Expiration
2040-06-05

AI Technical Summary

Benefits of technology

【0042】 本発明によれば、加工性と耐水性に優れるアクリルゴムベール及びその製造方法、該アクリルゴムベールを含んでなるゴム混合物及びその製造方法、並びにそれを架橋してなるゴム架橋物及びその製造方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610358000003
    Figure 0007610358000003
  • Figure 0007610358000004
    Figure 0007610358000004
  • Figure 0007610358000005
    Figure 0007610358000005
Patent Text Reader

Abstract

To provide an acrylic rubber bale excellent in processability and water resistance when kneading.SOLUTION: The acrylic rubber bale pertaining to the present invention comprises an acrylic rubber composed of (meth)acrylic acid ester as a main constituent, where the ash content is 0.3 wt.% or less, the content in the ash of at least 1 element selected from the group consisting of sodium, sulfur, calcium, magnesium, and phosphorus is 50 wt.% or more in total, and the gel amount insoluble to methyl ethyl ketone is 50 wt.% or less. The acrylic rubber bale can be produced by a method including the steps of: emulsifying monomer constituents composed of (meth)acrylic acid ester as a main constituent with water and an emulsifier; subjecting to emulsion polymerization in the presence of a polymerization catalyst; adding an obtained emulsion polymerization liquid into a coagulation liquid under a specific condition while stirring to generate a hydrous crumb; dehydrating and drying the obtained hydrous crumb after washing with warm water by a screw-type extruder; extruding as a dried rubber with a specific water content; and baling the obtained dried rubber.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an acrylic rubber veil and a method for producing the same, a rubber mixture and a method for producing the same, and a cross-linked rubber product, and more specifically to an acrylic rubber veil having excellent processability and water resistance and a method for producing the same, a rubber mixture containing the acrylic rubber veil and a method for producing the same, and a cross-linked rubber product obtained by cross-linking it. [Background technology]

[0002] Acrylic rubber is a polymer mainly composed of acrylic ester, and is generally known as a rubber with excellent heat resistance, oil resistance, and ozone resistance, and is widely used in the field of automobiles, etc. Such acrylic rubber is usually produced by emulsion polymerization of the monomer components constituting the acrylic rubber, contacting the obtained emulsion polymerization liquid with a coagulant, drying the obtained water-containing crumbs, and then baling them to produce a product.

[0003] Regarding acrylic rubber, for example, Patent Document 1 (JP 2006-328239 A) discloses a method for producing a rubber polymer, which comprises a step of obtaining a crumb slurry containing a crumb-like rubber polymer by contacting a polymer latex with a coagulation liquid, a step of crushing the crumb-like rubber polymer contained in the crumb slurry with a mixer equipped with a stirring and crushing function having a stirring power of 1 kW / m3 or more, a dehydration step of removing water from the crumb slurry in which the crumb-like rubber polymer is crushed to obtain a crumb-like rubber polymer, and a step of heating and drying the crumb-like rubber polymer from which the water has been removed, and it is described that the dried crumb is introduced in a baler in a flake form and compressed into a bale. It is also described that it is preferable to adjust the maximum width of the crumb to about 3 to 20 mm when crushing with a mixer equipped with a stirring and crushing function. The rubber polymer used here is specifically an unsaturated nitrile-conjugated diene copolymer latex obtained by emulsion polymerization, and it has also been shown to be applicable to copolymers composed only of acrylates, such as ethyl acrylate / n-butyl acrylate copolymer and ethyl acrylate / n-butyl acrylate / 2-methoxyethyl acrylate copolymer. However, acrylic rubber composed only of acrylates has the problem of being inferior in crosslinked rubber properties such as heat resistance and compression set resistance.

[0004] As an acrylic rubber having a reactive group that has excellent heat resistance and compression set resistance, for example, Patent Document 2 (International Publication No. 2018 / 116828 pamphlet) discloses a method in which a monomer component consisting of ethyl acrylate, n-butyl acrylate, and mono-n-butyl fumarate is emulsified with sodium lauryl sulfate as an emulsifier, polyethylene glycol monostearate, and water, and emulsion-polymerized in the presence of a polymerization initiator until a polymerization conversion rate of 95% is reached. The acrylic rubber latex is then added to an aqueous solution of magnesium sulfate and a polymer flocculant, dimethylamine-ammonia-epichlorohydrin polycondensate, and stirred at 85 ° C. to generate a crumb slurry, and then the crumb slurry is washed once with water and then passed through a 100-mesh wire net in its entirety to capture only the solid content and recover the crumb-like acrylic rubber. According to this method, the obtained hydrous crumb is dehydrated by centrifugation or the like, dried at 50 to 120°C by a band dryer or the like, and introduced into a baler, compressed, and baled. However, this method has problems such as the generation of a large amount of semi-coagulated hydrous crumb in the coagulation reaction, which adheres to the coagulation tank in large quantities, and the inability to sufficiently remove the coagulant and emulsifier by washing. Even if a bale is produced, it has poor water resistance and poor processability in a Banbury or the like, requiring a long kneading time.

[0005] In addition, Patent Document 3 (International Publication No. 2018 / 079783) discloses a method for producing an acrylic rubber having excellent water resistance (volume change after immersion in distilled water at 80 ° C. for 70 hours) with little residual emulsifier or coagulant by emulsifying monomer components consisting of ethyl acrylate, n-butyl acrylate, and mono-n-butyl fumarate using pure water and an emulsifier consisting of sodium lauryl sulfate and polyoxyethylene dodecyl ether, and emulsion-polymerizing the monomer components to a polymerization conversion rate of 95% by weight in the presence of a polymerization initiator to obtain an emulsion polymerization liquid, and then continuously adding sodium sulfate to produce a water-containing crumb. The water-containing crumb thus produced is then washed four times with industrial water, washed once with an acid of pH 3, and washed once with pure water, and then dried in a hot air dryer at 110 ° C. for 1 hour. However, there is no description of using the obtained acrylic rubber in a veil shape, and there is a problem that handling the sticky acrylic rubber in a crumb shape is poor in workability and storage stability. Furthermore, the obtained acrylic rubber is inferior in processability, and with regard to water resistance, a high level of water resistance is required in harsher environments.

[0006] Regarding the gel content of acrylic rubber, for example, Patent Document 4 (JP Patent No. 3599962) discloses an acrylic rubber having an acetone-insoluble gel fraction of 5% by weight or less obtained by copolymerizing 95-99.9% by weight of alkyl acrylate or alkoxyalkyl acrylate with 0.1-5% by weight of a polymerizable monomer having two or more radically reactive unsaturated groups with different reactivity in the presence of a radical polymerization initiator, a reinforcing filler, and an organic peroxide-based vulcanizing agent, and an acrylic rubber composition having excellent extrusion processability such as extrusion speed, die swell, and surface texture. The acrylic rubber with a very small gel fraction used here is said to be obtained by adjusting the polymerization solution to pH 6-8 with sodium bicarbonate or the like, as opposed to an acrylic rubber with a high gel fraction (60%) obtained in a normal acidic range (pH 4 before polymerization, pH 3.4 after polymerization). Specifically, water, sodium lauryl sulfate and polyoxyethylene nonylphenyl ether as emulsifiers, sodium carbonate, and boric acid are charged and adjusted to 75°C, then t-butyl hydroperoxide, Rongalite, disodium ethylenediaminetetraacetate, and ferrous sulfate are added (pH at this time is 7.1), and then the monomer components of ethyl acrylate and allyl methacrylate are added dropwise to carry out emulsion polymerization, and the resulting emulsion with a pH of 7 is salted out using an aqueous sodium sulfate solution, washed with water, and dried to obtain acrylic rubber. However, the acrylic rubber obtained by this method has problems with handling, such as decomposition in the neutral to alkaline range, poor storage stability, and poor water resistance.

[0007] In addition, Patent Document 5 (International Publication No. WO 2018 / 143101) discloses a technique for improving the extrusion moldability, particularly the discharge amount, discharge length, and surface texture, of a rubber composition containing a reinforcing agent and a crosslinking agent, by emulsion polymerization of a (meth)acrylic acid ester and an ion-crosslinkable monomer, using an acrylic rubber having a complex viscosity at 100 ° C. ([η]100 ° C.) of 3,500 Pa·s or less and a ratio ([η]100 ° C. / [η]60 ° C.) of the complex viscosity at 60 ° C. ([η]60 ° C.) to the complex viscosity at 100 ° C. ([η]100 ° C.) of 0.8 or less. The gel content of the tetrahydrofuran insoluble portion of the acrylic rubber used in this technique is 80% by weight or less, preferably 5 to 80% by weight, but is preferably present as much as possible within the range of 70% by weight or less, and it is described that the extrusion property deteriorates when the gel content is less than 5%. The patent also describes that the weight-average molecular weight (Mw) of the acrylic rubber used is 200,000 to 1,000,000, and that if the weight-average molecular weight (Mw) exceeds 1,000,000, the viscoelasticity of the acrylic rubber becomes too high, which is undesirable. However, the patent document does not describe a method for improving the water resistance of the acrylic rubber or the kneading processability in a Banbury mixer, or making the acrylic rubber into a sheet or veil.

[0008] On the other hand, for example, Patent Document 6 (JP Patent Publication 1-225512 A) discloses a method for producing sheet-shaped acrylic rubber, in which a twin-screw extruder dryer consisting of a feed barrel, a dehydration barrel, a standard barrel, a vent barrel, and a vacuum barrel is used to feed nitrile rubber (NBR) crumbs with a water content of about 50% to the feed barrel, and after most of the water is dehydrated in the dehydration barrel, the remaining water and evaporated vapor are removed by suction in the vacuum barrel, and the crumbs are continuously extruded in a strip shape through a breaker plate and a die, and it is described that acrylic rubber crumbs are used as the rubber crumbs to be applied. However, the same Patent Document does not disclose the use of such acrylic rubber sheets to form bales. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2006-328239 A [Patent Document 2] International Publication No. 2018 / 116828 Brochure [Patent Document 3] International Publication No. 2018 / 079783 Brochure [Patent Document 4] Patent No. 3599962 [Patent Document 5] International Publication No. 2018 / 143101 Brochure [Patent Document 6] Japanese Patent Application Publication No. 1-225512 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention has been made in consideration of the above-mentioned circumstances, and has an object to provide an acrylic rubber veil that exhibits excellent water resistance and processability when kneaded with a Banbury mixer or the like and a production method thereof, a rubber mixture containing the acrylic rubber veil and a production method thereof, and a cross-linked rubber product thereof. [Means for solving the problem]

[0011] The present inventors conducted intensive research in light of the above-mentioned problems and discovered that an acrylic rubber veil made of an acrylic rubber containing a (meth)acrylic acid ester as a main component, in which the ash content, the amount of specific elements in the ash content, and the amount of gel of the specific solvent-insoluble matter have been specified, has excellent kneading processability in a Banbury mixer or the like, and excellent water resistance.

[0012] The present inventors have also discovered that by specifying the amount of reactive groups in the acrylic rubber that constitutes the acrylic rubber veil, and by specifying the pH, complex viscosity at a specific temperature, specific gravity, and water content of the acrylic rubber veil, the processability and water resistance of the acrylic rubber veil can be further improved, and the handleability as an acrylic rubber veil can be significantly improved.

[0013] The present inventors have also discovered that such acrylic rubber bales can be easily produced by adding an emulsion polymerization liquid obtained by emulsion-polymerizing a monomer component mainly composed of a (meth)acrylic acid ester to a stirred coagulation liquid to produce water-containing crumbs, washing the washed water-containing crumbs with warm water, melt-drying the washed water-containing crumbs until they reach a specific water content using a screw-type dissolving machine, and baling the extruded dried rubber.

[0014] The inventors have also discovered that water resistance is dramatically improved by providing a dehydration step in which water is squeezed out of the washed hydrous crumbs, and that the handleability of the acrylic rubber bale is dramatically improved and processability is also enhanced by including a reactive group-containing monomer in the monotonous component, raising the polymerization conversion rate of the emulsion polymerization to a specific level or higher, and forming the dried rubber extruded from the screw-type extruder into a sheet.

[0015] The present inventors have further discovered that it is difficult to control the gel amount of the specific solvent-insoluble component of acrylic rubber during production, and that in particular when an attempt is made to increase the molecular weight of the acrylic rubber by increasing the polymerization conversion rate in order to improve the handleability of the acrylic rubber bale, the gel amount of the specific solvent-insoluble component increases rapidly, thereby worsening the processability of the acrylic rubber bale, but that this rapidly increased gel of the specific solvent-insoluble component disappears when the water-containing crumbs are dried in a screw-type extruder until they are substantially free of moisture (specific moisture content) and then melt-kneaded, and that while it is difficult to dry acrylic rubber, which has a low specific heat, to a specific moisture content in a screw-type extruder, it is possible to reliably reduce the gel amount of the specific solvent-insoluble component in the obtained acrylic rubber bale by raising the temperature of the water-containing crumbs to a specific level or higher, thereby making it possible to significantly improve processability, and that the gel amount in the acrylic rubber bale varies entirely depending on the solvent used, and that, for example, the gel amounts of acetone, tetrahydrofuran and methyl ethyl ketone-insoluble components are not correlated and also impart completely different properties to the acrylic rubber bale.

[0016] Based on these findings, the present inventors have completed the present invention.

[0017] Thus, according to the present invention, Obtained by emulsion polymerization,(Meth)acrylic acid esters and a structural unit having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group. Made of acrylic rubber, The acrylic rubber is measured according to JIS K6288 Method A. The ash content is 0.0001~ 0.3 weight %in The total content of at least one element selected from the group consisting of sodium, sulfur, calcium, magnesium and phosphorus in the ash is 50% by weight or more, and the gel content of the methyl ethyl ketone insoluble matter is 50% by weight or less. , having a rectangular parallelepiped shape An acrylic rubber veil is provided.

[0018] In the acrylic rubber veil of the present invention, the ash content is preferably 0.2% by weight or less.

[0019] In the acrylic rubber veil of the present invention, the acrylic rubber is Contains sodium and sulfur in ash It is preferable stomach. In the acrylic rubber veil of the present invention, The reactive group content of the acrylic rubber is 0.001 ~5% by weight It is preferable that there is.

[0020] In the acrylic rubber veil of the present invention, the weight average molecular weight (Mw) of the acrylic rubber is preferably in the range of 1,000,000 to 5,000,000.

[0021] In the acrylic rubber veil of the present invention, the amount of gel insoluble in methyl ethyl ketone is preferably 30% by weight or less.

[0022] In the acrylic rubber veil of the present invention, it is more preferable that the gel amount of the methyl ethyl ketone-insoluble matter is 20% by weight or less.

[0023] In the acrylic rubber veil of the present invention, For total ash content The total amount of sodium and sulfur in the ash is preferably 80% by weight or more.

[0024] In the acrylic rubber veil of the present invention, the ratio of sodium to sulfur in the ash ([Na] / [S]) is preferably in the range of 0.75 to 0.95 by weight.

[0025] In the acrylic rubber veil of the present invention, the pH is 2 to 6 It is preferable that there is.

[0026] In the acrylic rubber veil of the present invention, It is preferable that the complex viscosity at 100°C ([η]100°C) is 1,500 to 6,000 Pa·s, and the ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is 0.5 to 0.99. Here, the complex viscosity is measured by measuring the temperature dispersion (40 to 120°C) at a strain of 473% and 1 Hz using a dynamic viscoelasticity measuring device "Rubber Process Analyzer RPA-2000" (manufactured by Alpha Technology Co., Ltd.), obtaining the complex viscosity η at each temperature, and the dynamic viscoelasticity at 60°C of the above-mentioned dynamic viscoelasticity is defined as the complex viscosity [η]60°C, and the dynamic viscoelasticity at 100°C is defined as the complex viscosity [η]100°C. In the acrylic rubber veil of the present invention, it is more preferable that the ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is 0.83 or more.

[0027] In the acrylic rubber veil of the present invention, Measured according to JIS K6268 Crosslinked Rubber - Density Measurement Method A The specific gravity is preferably in the range of 0.7 to 1.5, and the water content is preferably less than 1% by weight.

[0028] In the acrylic rubber veil of the present invention, the acrylic rubber is preferably one which has been emulsion-polymerized using a sulfate ester salt as an emulsifier. In the acrylic rubber veil of the present invention, the acrylic rubber is preferably polymerized with an organic peroxide or an inorganic peroxide. 17. The acrylic rubber veil of the present invention according to any one of claims 1 to 16, wherein the acrylic rubber is polymerized at a polymerization conversion rate of 80% by weight or more. In the acrylic rubber veil of the present invention, the acrylic rubber is subjected to emulsion polymerization, and then the polymerization solution is coagulated with a sodium salt coagulant to generate water-containing crumbs. Dehydrate It is preferably dry. In the acrylic rubber veil of the present invention, Acrylic rubber is Of the generated water-containing crumbs, the proportion of those that pass through a JIS sieve with a mesh size of 6.7 mm but do not pass through a JIS sieve with a mesh size of 710 μm is 20% by weight or more. It is made from crumbs. It is preferred. In the acrylic rubber veil of the present invention, the acrylic rubber is Over 40℃ It is preferable that the material is washed with warm water and then dried. In the acrylic rubber veil of the present invention, the drying is preferably carried out by melt kneading. In the acrylic rubber veil of the present invention, the melt kneading is Moisture content less than 1% by weight It is preferable that the above-mentioned method is carried out in a non-contact state. In the acrylic rubber veil of the present invention, the drying is preferably carried out in a screw-type extruder. In the acrylic rubber veil of the present invention, it is preferable that after the drying, it is cooled at a cooling rate of 50° C. / hr or more.

[0029] According to the present invention, a monomer component mainly composed of a (meth)acrylic acid ester is and a monomer component having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group, an emulsion polymerization step of emulsifying the above with water and an emulsifier, and emulsion-polymerizing the emulsion in the presence of a polymerization catalyst to obtain an emulsion polymerization liquid; a coagulation step of adding the obtained emulsion polymerization liquid to a stirred coagulation liquid to produce water-containing crumbs; Over 40℃ The washing process involves washing the crumbs with warm water, and the washing process involves extruding the crumbs using a screw extruder. Dehydrate and dry, Dry rubber that has been dried to a moisture content of less than 1% by weight As The extrusion drying process and the extruded dried rubber Form into a rectangular bale and binging the acrylic rubber veil. In the method for producing an acrylic rubber veil of the present invention, it is preferable to produce the above-mentioned acrylic rubber veil.

[0030] In the method for producing an acrylic rubber veil of the present invention, The emulsifier or coagulant contains at least one element selected from the group consisting of sodium, sulfur, calcium, magnesium and phosphorus. It is preferred.

[0031] In the method for producing an acrylic rubber veil of the present invention, the polymerization conversion rate of the emulsion polymerization is preferably 90% by weight or more.

[0032] In the method for producing an acrylic rubber bale according to the present invention, the temperature of the water-containing crumb fed into the screw-type extruder is 40 to 50° C. At 100°C It is also preferable to provide a dehydration step for squeezing out the water from the hydrous crumb.

[0033] Furthermore, in the method for producing an acrylic rubber veil of the present invention, it is preferable that the dehydration of the water-containing crumb is carried out until the water content reaches 1 to 40% by weight.

[0034] In the method for producing an acrylic rubber veil of the present invention, it is more preferable that the water content after dehydration is in the range of 5 to 35% by weight.

[0035] In the method for producing an acrylic rubber veil of the present invention, it is preferable that the degree of vacuum in the drying barrel of the screw-type extruder is in the range of 1 to 50 kPa, and the drying temperature is in the range of 100 to 250°C.

[0036] In the method for producing an acrylic rubber veil of the present invention, it is preferable that the moisture content of the moisture crumb at the die portion of the screw-type extruder is less than 1% by weight.

[0037] In the method for producing an acrylic rubber veil of the present invention, the resin pressure at the die of the screw-type extruder is preferably in the range of 0.1 to 10 MPa.

[0038] In the method for producing an acrylic rubber veil of the present invention, the ratio (Q / N) of the extrusion rate (Q) to the rotation speed (N) of the screw-type extruder is preferably in the range of 2-10.

[0039] In the method for producing an acrylic rubber veil of the present invention, the dried rubber is preferably in the form of a sheet.

[0040] According to the present invention, there is also provided a rubber mixture obtained by mixing the acrylic rubber veil with a filler and a crosslinking agent. In the rubber mixture according to the invention, the filler is preferably a reinforcing filler. In the rubber mixture according to the invention, the filler is preferably carbon black. In the rubber mixture according to the invention, the filler is preferably silica. In the rubber mixture of the present invention, the crosslinking agent is preferably a polyamine compound, an ammonium carboxylate, a metal dithiocarbamate or a triazine thiol compound. It is preferable that an antioxidant is further mixed into the rubber mixture of the present invention. In the rubber mixture of the present invention, the antioxidant is preferably an amine-based antioxidant. Further, according to the present invention, the acrylic rubber veil is provided with a filler.、 Crosslinking Agent and antioxidants as necessary and a method for producing a rubber mixture, comprising mixing the acrylic rubber veil and a filler in a mixer. and antioxidants as needed The present invention provides a method for preparing a rubber mix in which the crosslinking agent is mixed after the mixing of the above-mentioned components.

[0041] According to the present invention, there is further provided a cross-linked rubber product obtained by cross-linking the above rubber mixture. In the cross-linked rubber product of the present invention, the cross-linking preferably includes a primary cross-linking and a secondary cross-linking. According to the present invention, there is further provided a method for producing a cross-linked rubber product, which comprises subjecting the above-mentioned rubber mixture to primary cross-linking and then secondary cross-linking. Effect of the Invention

[0042] According to the present invention, there is provided an acrylic rubber veil having excellent processability and water resistance and a method for producing the same, a rubber mixture containing the acrylic rubber veil and a method for producing the same, and a cross-linked rubber product obtained by cross-linking the rubber mixture. And its manufacturing method is provided. [Brief description of the drawings]

[0043] [Figure 1] FIG. 1 is a diagram illustrating an example of an acrylic rubber production system used to produce an acrylic rubber veil according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing the configuration of the screw-type extruder in FIG. 1. [Diagram 3] FIG. 2 is a diagram showing the configuration of a transportable cooling device used as the cooling device in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0044] The acrylic rubber veil of the present invention is characterized in that it is made of an acrylic rubber containing a (meth)acrylic acid ester as a main component, has an ash content of 0.3% by weight or less, has a total content of at least one element selected from sodium, sulfur, calcium, magnesium and phosphorus in the ash of 50% by weight or more, and has a gel content of 50% by weight or less of a methyl ethyl ketone-insoluble matter.

[0045] <Monomer components> The acrylic rubber constituting the acrylic rubber veil of the present invention is mainly composed of (meth)acrylic acid ester. The ratio of (meth)acrylic acid ester in the acrylic rubber is appropriately selected depending on the purpose of use, but is usually 50% by weight or more, preferably 70% by weight or more, and more preferably 80% by weight or more. In the present invention, the term "(meth)acrylic acid ester" is a general term for esters of acrylic acid and / or methacrylic acid.

[0046] The acrylic rubber constituting the acrylic rubber veil of the present invention contains at least one (meth)acrylic ester selected from (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, and is suitable because it can highly improve the crosslinking properties of the acrylic rubber veil.

[0047] The acrylic rubber constituting the acrylic rubber veil of the present invention is preferably one containing a reactive group-containing monomer, since this can highly improve the heat resistance, compression set resistance, and other properties.

[0048] Preferred specific examples of the acrylic rubber constituting the acrylic rubber veil of the present invention include those composed of at least one (meth)acrylic acid ester selected from (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a reactive group-containing monomer, and, if necessary, other copolymerizable monomers.

[0049] The (meth)acrylic acid alkyl ester is not limited, but is usually a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 12 carbon atoms, preferably a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 8 carbon atoms, and more preferably a (meth)acrylic acid alkyl ester having an alkyl group having 2 to 6 carbon atoms.

[0050] Specific examples of such (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, and the like, with ethyl (meth)acrylate and n-butyl (meth)acrylate being preferred, and ethyl acrylate and n-butyl acrylate being more preferred.

[0051] In addition, the (meth)acrylic acid alkoxyalkyl ester is not limited, but is usually a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group of 2 to 12, preferably a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group of 2 to 8, and more preferably a (meth)acrylic acid alkoxyalkyl ester having an alkoxyalkyl group of 2 to 6 carbon atoms.

[0052] Specific examples of such (meth)acrylic acid alkoxyalkyl esters include methoxymethyl (meth)acrylate, methoxyethyl (meth)acrylate, methoxypropyl (meth)acrylate, methoxybutyl (meth)acrylate, ethoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, etc. Among these, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate, etc. are preferred, and methoxyethyl acrylate, ethoxyethyl acrylate, etc. are more preferred.

[0053] At least one (meth)acrylic acid ester selected from these (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters is used alone or in combination of two or more, and the ratio of the (meth)acrylic acid ester in the acrylic rubber is usually 50 to 99.99% by weight, preferably 70 to 99.9% by weight, more preferably 80 to 99.5% by weight, and most preferably 87 to 99% by weight. If the amount of the (meth)acrylic acid ester in the monomer component is excessively small, the weather resistance, heat resistance, and oil resistance of the obtained acrylic rubber may decrease, which is not preferable.

[0054] The reactive group-containing monomer is not limited and may be appropriately selected depending on the intended use, but is preferably a monomer having at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group, and more preferably a monomer having at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom.

[0055] The monomer having a carboxyl group is not limited, but an ethylenically unsaturated carboxylic acid can be suitably used. Examples of the ethylenically unsaturated carboxylic acid include ethylenically unsaturated monocarboxylic acid, ethylenically unsaturated dicarboxylic acid, and ethylenically unsaturated dicarboxylic acid monoester, and among these, ethylenically unsaturated dicarboxylic acid monoester is particularly preferred because it can further improve the compression set resistance property when the acrylic rubber is made into a rubber cross-linked product.

[0056] The ethylenically unsaturated monocarboxylic acid is not limited, but is preferably an ethylenically unsaturated monocarboxylic acid having 3 to 12 carbon atoms, and examples thereof include acrylic acid, methacrylic acid, α-ethylacrylic acid, crotonic acid, and cinnamic acid.

[0057] The ethylenically unsaturated dicarboxylic acid is not limited, but is preferably an ethylenically unsaturated dicarboxylic acid having 4 to 12 carbon atoms, and examples thereof include butenedioic acids such as fumaric acid and maleic acid, itaconic acid, citraconic acid, etc. The ethylenically unsaturated dicarboxylic acid also includes those that exist as an anhydride.

[0058] The ethylenically unsaturated dicarboxylic acid monoester is not limited, but is usually an ethylenically unsaturated dicarboxylic acid having 4 to 12 carbon atoms and an alkyl monoester having 1 to 12 carbon atoms, preferably an ethylenically unsaturated dicarboxylic acid having 4 to 6 carbon atoms and an alkyl monoester having 2 to 8 carbon atoms, and more preferably an alkyl monoester having 2 to 6 carbon atoms of butenedioic acid having 4 carbon atoms.

[0059] Specific examples of such ethylenically unsaturated dicarboxylic acid monoesters include butenedioic acid monoalkyl esters such as monomethyl fumarate, monoethyl fumarate, mono-n-butyl fumarate, monomethyl maleate, monoethyl maleate, mono-n-butyl maleate, monocyclopentyl fumarate, monocyclohexyl fumarate, monocyclohexenyl fumarate, monocyclopentyl maleate, and monocyclohexyl maleate; and itaconic acid monoalkyl esters such as monomethyl itaconate, monoethyl itaconate, mono-n-butyl itaconate, and monocyclohexyl itaconate; and among these, mono-n-butyl fumarate and mono-n-butyl maleate are preferred, and mono-n-butyl fumarate is particularly preferred.

[0060] Examples of the monomer having an epoxy group include epoxy group-containing (meth)acrylic acid esters such as glycidyl (meth)acrylate; epoxy group-containing vinyl ethers such as allyl glycidyl ether and vinyl glycidyl ether; and the like.

[0061] Examples of monomers having a halogen group include unsaturated alcohol esters of halogen-containing saturated carboxylic acids, (meth)acrylic acid haloalkyl esters, (meth)acrylic acid haloacyloxyalkyl esters, (meth)acrylic acid (haloacetylcarbamoyloxy)alkyl esters, halogen-containing unsaturated ethers, halogen-containing unsaturated ketones, halomethyl group-containing aromatic vinyl compounds, halogen-containing unsaturated amides, and haloacetyl group-containing unsaturated monomers.

[0062] Specific examples of the unsaturated alcohol ester of the halogen-containing saturated carboxylic acid include vinyl chloroacetate, vinyl 2-chloropropionate, and allyl chloroacetate.Specific examples of the (meth)acrylic acid haloalkyl ester include chloromethyl (meth)acrylate, 1-chloroethyl (meth)acrylate, 2-chloroethyl (meth)acrylate, 1,2-dichloroethyl (meth)acrylate, 2-chloropropyl (meth)acrylate, 3-chloropropyl (meth)acrylate, and 2,3-dichloropropyl (meth)acrylate.Specific examples of the (meth)acrylic acid haloacyloxyalkyl ester include 2-(chloroacetoxy)ethyl (meth)acrylate, 2-(chloroacetoxy)propyl (meth)acrylate, 3-(chloroacetoxy)propyl (meth)acrylate, and 3-(hydroxychloroacetoxy)propyl (meth)acrylate. Examples of (meth)acrylic acid (haloacetylcarbamoyloxy) alkyl esters include 2-(chloroacetylcarbamoyloxy) ethyl (meth)acrylate and 3-(chloroacetylcarbamoyloxy) propyl (meth)acrylate. Specific examples of halogen-containing unsaturated ethers include chloromethyl vinyl ether, 2-chloroethyl vinyl ether, 3-chloropropyl vinyl ether, 2-chloroethyl allyl ether, and 3-chloropropyl allyl ether. Specific examples of halogen-containing unsaturated ketones include 2-chloroethyl vinyl ketone, 3-chloropropyl vinyl ketone, and 2-chloroethyl allyl ketone. Specific examples of halomethyl group-containing aromatic vinyl compounds include p-chloromethylstyrene, m-chloromethylstyrene, o-chloromethylstyrene, and p-chloromethyl-α-methylstyrene. Specific examples of halogen-containing unsaturated amides include N-chloromethyl(meth)acrylamide. Specific examples of the haloacetyl group-containing unsaturated monomer include 3-(hydroxychloroacetoxy)propyl allyl ether and p-vinylbenzyl chloroacetate.

[0063] These reactive group-containing monomers may be used alone or in combination of two or more, and their proportion in the acrylic rubber is usually 0.01 to 20% by weight, preferably 0.1 to 10% by weight, more preferably 0.5 to 5% by weight, and most preferably 1 to 3% by weight.

[0064] Other monomers (hereinafter referred to as "other monomers") other than those mentioned above that are used as necessary are not particularly limited as long as they are copolymerizable with the above-mentioned monomers, and examples thereof include aromatic vinyl, ethylenically unsaturated nitriles, acrylamide monomers, other olefin monomers, etc. Examples of aromatic vinyl include styrene, α-methylstyrene, divinylbenzene, etc. Examples of ethylenically unsaturated nitriles include acrylonitrile, methacrylonitrile, etc. Examples of acrylamide monomers include acrylamide, methacrylamide, etc. Examples of other olefin monomers include ethylene, propylene, vinyl acetate, ethyl vinyl ether, butyl vinyl ether, etc.

[0065] These other monomers may be used alone or in combination of two or more, and their proportion in the acrylic rubber is usually in the range of 0 to 30% by weight, preferably 0 to 20% by weight, more preferably 0 to 15 parts by weight, and most preferably 0 to 10 parts by weight.

[0066] <Acrylic rubber> The acrylic rubber constituting the acrylic rubber veil of the present invention preferably has a reactive group in the polymer.

[0067] The reactive group is not particularly limited and may be appropriately selected depending on the intended use, but is preferably at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group, more preferably at least one functional group selected from the group consisting of a carboxyl group, an epoxy group, and a chlorine atom, which is suitable for highly improving the crosslinking properties of the acrylic rubber veil. The acrylic rubber having such a reactive group may be one in which a reactive group is imparted to the acrylic rubber by a post-reaction, but is preferably one obtained by copolymerizing a reactive group-containing monomer.

[0068] The content of reactive groups in the acrylic rubber (polymer) may be appropriately selected depending on the purpose of use, but when the weight ratio of the reactive groups themselves is usually 0.001 or more, preferably 0.001 to 5 wt%, more preferably 0.01 to 3 wt%, particularly preferably 0.05 to 1 wt%, and most preferably in the range of 0.1 to 0.5 wt%, it is suitable in that properties such as processability, strength properties, compression set resistance, oil resistance, cold resistance, and water resistance are highly balanced.

[0069] Specific examples of the acrylic rubber constituting the acrylic rubber veil of the present invention include at least one (meth)acrylic ester selected from (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, a reactive monomer, and other copolymerizable monomers contained as necessary, and the proportions of each in the acrylic rubber are usually 50 to 99.99% by weight, preferably 70 to 99.9% by weight, more preferably 80 to 99.5% by weight, and particularly preferably 87 to 99% by weight, of the at least one (meth)acrylic ester selected from (meth)acrylic acid alkyl esters and (meth)acrylic acid alkoxyalkyl esters, the reactive monomer is usually 0.01 to 20% by weight, preferably 0.1 to 10% by weight, more preferably 0.5 to 5% by weight, and particularly preferably 1 to 3% by weight, and the other monomers are usually 0 to 30% by weight, preferably 0 to 20% by weight, more preferably 0 to 15% by weight, and particularly preferably 0 to 10% by weight. By setting the content of these monomers in the acrylic rubber within the above ranges, the object of the present invention can be achieved to a high degree, and the water resistance and compression set resistance properties are significantly improved when the acrylic rubber veil is crosslinked, which is preferable.

[0070] The weight average molecular weight (Mw) of the acrylic rubber constituting the acrylic rubber veil of the present invention is not limited, but when the absolute molecular weight measured by GPC-MALS is usually in the range of 100,000 to 5,000,000, preferably 500,000 to 5,000,000, more preferably 1,000,000 to 5,000,000, particularly preferably 1,100,000 to 3,500,000, and most preferably 1,200,000 to 2,500,000, the processability during mixing of the acrylic rubber veil, strength properties, and compression set resistance properties are highly balanced and suitable.

[0071] There are no limitations on the ratio (Mz / Mw) of the z-average molecular weight (Mz) to the weight-average molecular weight (Mw) of the acrylic rubber constituting the acrylic rubber veil of the present invention, but when the ratio is usually 1.3 or more, preferably 1.4 to 5, and more preferably 1.5 to 2, in terms of absolute molecular weight distribution with emphasis on the high molecular weight region measured by GPC-MALS, it is suitable because this allows the processability and strength characteristics of the acrylic rubber veil to be highly balanced and also mitigates changes in physical properties during storage.

[0072] The glass transition temperature (Tg) of the acrylic rubber constituting the acrylic rubber veil of the present invention is not limited, but is usually 20° C. or lower, preferably 10° C. or lower, and more preferably 0° C. or lower. The lower limit of the glass transition temperature (Tg) of the acrylic rubber is not particularly limited, but is usually −80° C. or higher, preferably −60° C. or higher, and more preferably −40° C. or higher. By setting the glass transition temperature at or above the above lower limit, the oil resistance and heat resistance can be improved, and by setting it at or below the above upper limit, the cold resistance and processability can be improved.

[0073] The content of the acrylic rubber in the acrylic rubber veil of the present invention is appropriately selected depending on the purpose of use, but is usually 95% by weight or more, preferably 97% by weight or more, and more preferably 98% by weight or more. The content of the acrylic rubber in the acrylic rubber veil of the present invention is approximately the same as the total amount of the acrylic rubber veil minus the amount of ash that was not completely removed by the emulsifier and coagulant used in the production.

[0074] <Acrylic rubber veil> The acrylic rubber veil of the present invention is characterized in that it is made of the above-mentioned acrylic rubber, and contains an ash content, an ash component content, and a gel content, all of which are within specific ranges. The ash content in the acrylic rubber veil is measured in accordance with JIS K6228 Method A, and the main components are residues of an emulsifier used in emulsifying and emulsion-polymerizing the monomer components in the production of acrylic rubber, and a coagulant used in coagulating the emulsion polymerization liquid.

[0075] The size of the acrylic rubber veil of the present invention is not limited, but the width is usually within the range of 100 to 800 mm, preferably 200 to 500 mm, and more preferably 250 to 450 mm, the length is usually within the range of 300 to 1,200 mm, preferably 400 to 1,000 mm, and more preferably 500 to 800 mm, and the height is usually within the range of 50 to 500 mm, preferably 100 to 300 mm, and more preferably 150 to 250 mm. The shape of the acrylic rubber veil of the present invention is also not limited and may be appropriately selected depending on the purpose of use of the acrylic rubber veil, but in many cases a rectangular parallelepiped is suitable.

[0076] The acrylic rubber veil of the present invention has an ash content of 0.3% by weight or less, preferably 0.25% by weight or less, more preferably 0.2% by weight or less, particularly preferably 0.15% by weight or less, and most preferably 0.12% by weight or less, which is suitable for achieving excellent storage stability and water resistance.

[0077] The lower limit of the ash content in the acrylic rubber veil of the present invention is not limited, but is usually 0.0001% by weight or more, preferably 0.0005% by weight or more, more preferably 0.001% by weight or more, particularly preferably 0.005% by weight or more, and most preferably 0.01% by weight or more, which is preferable because it suppresses metal adhesion and provides excellent workability. For example, the preferred range of the ash content for achieving a high level of balance between the water resistance and metal adhesion of the acrylic rubber veil can be said to be 0.0001 to 0.15% by weight.

[0078] The ash content, which provides a high level of balance between storage stability, water resistance and workability of the acrylic rubber veil of the present invention, is usually in the range of 0.0001 to 0.3% by weight, preferably 0.0005 to 0.25% by weight, more preferably 0.001 to 0.25% by weight, particularly preferably 0.005 to 0.15% by weight, and most preferably 0.01 to 0.12% by weight.

[0079] The acrylic rubber veil of the present invention has an ash content of at least one element selected from sodium, sulfur, calcium, magnesium and phosphorus of at least 30% by weight in total. When the total content of these elements is 30% by weight or more, preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 80% by weight or more, the acrylic rubber veil has excellent storage stability and water resistance.

[0080] In particular, the total amount of sodium and sulfur in the ash of the acrylic rubber veil of the present invention is not particularly limited, but when it is usually 30% by weight or more, preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 80% by weight or more, the storage stability and water resistance are remarkably excellent and it is suitable.

[0081] The ratio of sodium to sulfur in the ash of the acrylic rubber veil of the present invention ([Na] / [S]) is not particularly limited, but when it is in the range of usually 0.4 to 2.5, preferably 0.6 to 1, more preferably 0.7 to 0.98, particularly preferably 0.75 to 0.95, and most preferably 0.8 to 0.9 by weight, water resistance is highly excellent and it is suitable.

[0082] The gel content of the acrylic rubber veil of the present invention, in terms of the insoluble matter in methyl ethyl ketone, is 50% by weight or less, preferably 30% by weight or less, more preferably 20% by weight or less, particularly preferably 10% by weight or less, and most preferably 5% by weight or less. A gel content within this range is preferable because it highly improves processability during kneading in a Banbury mixer or the like.

[0083] The water content of the acrylic rubber veil of the present invention is not limited, but when it is generally less than 1% by weight, preferably 0.8% by weight or less, and more preferably 0.6% by weight or less, the vulcanization characteristics are optimized and properties such as heat resistance and water resistance are highly excellent, making it suitable.

[0084] The specific gravity of the acrylic rubber veil of the present invention is not limited, but when it is in the range of usually 0.7 to 1.5, preferably 0.8 to 1.4, more preferably 0.9 to 1.3, particularly preferably 0.95 to 1.25, and most preferably 1.0 to 1.2, the storage stability is highly excellent and it is suitable.

[0085] The pH of the acrylic rubber veil of the present invention is not limited, but is usually 6 or less, preferably 2 to 6, more preferably 2.5 to 5.5, and particularly preferably 3 to 5, and is therefore suitable since storage stability is highly improved.

[0086] The complex viscosity at 60°C of the acrylic rubber veil of the present invention ([η]60°C) is not limited, but is usually 15,000 Pa·s or less, preferably 2,000 to 10,000 Pa·s, more preferably 2,500 to 7,000 Pa·s, and most preferably 2,700 to 5,500 Pa·s, which is preferable in terms of excellent processability, oil resistance, and shape retention. The complex viscosity at 100°C ([η]100°C) is usually 1,500 to 6,000 Pa·s, preferably 2,000 to 5,000 Pa·s, more preferably 2,500 to 4,000 Pa·s, and most preferably 2,500 to 3,500 Pa·s, which is preferable in terms of excellent processability, oil resistance, and shape retention.

[0087] The ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) of the acrylic rubber veil of the present invention is not limited, but is usually 0.5 or more, preferably 0.6 or more, more preferably 0.7 or more, particularly preferably 0.8 or more, and most preferably 0.83 or more. In addition, when the ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is usually in the range of 0.5 to 0.99, preferably 0.5 to 0.98, more preferably 0.6 to 0.95, and most preferably 0.75 to 0.93, the processability, oil resistance, and shape retention are highly balanced and are suitable.

[0088] The Mooney viscosity (ML1+4, 100°C) of the acrylic rubber veil is not limited, but when it is in the range of usually 10 to 150, preferably 20 to 100, and more preferably 25 to 70, the processability and strength properties are highly balanced and it is suitable.

[0089] <Manufacturing method of acrylic rubber veil> The acrylic rubber veil can be easily produced by the production method of the present invention, which includes the following steps: (a) an emulsion polymerization step of emulsifying a monomer component mainly composed of a (meth)acrylic acid ester with water and an emulsifier, and emulsion-polymerizing the resulting emulsion in the presence of a polymerization catalyst to obtain an emulsion polymerization liquid; (b) a coagulation step in which the obtained emulsion polymerization liquid is added to a stirred coagulation liquid to produce water-containing crumbs; (c) a washing step of washing the generated hydrous crumbs with warm water; (d) a drying step in which the washed wet crumbs are dried to a water content of less than 1% by weight using a screw-type extruder to extrude a dried rubber; (e) a baling step for baling the extruded dry rubber; The acrylic rubber veil can be produced by a method for producing the acrylic rubber veil comprising the steps of:

[0090] (Emulsion polymerization process) The emulsion polymerization step in the method for producing an acrylic rubber veil of the present invention is characterized in that the above-mentioned monomer components are emulsified with water and an emulsifier, and then emulsion-polymerized in the presence of a polymerization catalyst to obtain an emulsion polymerization liquid.

[0091] The emulsifier used in the emulsion polymerization step is not limited and may be any of the usual methods, and examples thereof include anionic emulsifiers, cationic emulsifiers, nonionic emulsifiers, etc. Among these, anionic emulsifiers and nonionic emulsifiers are preferred, anionic emulsifiers are particularly preferred, and sulfuric acid-based emulsifiers are most preferred.

[0092] The anionic emulsifier is not limited and any commonly used one can be used, but examples thereof include fatty acid-based emulsifiers, sulfonic acid-based emulsifiers, sulfosuccinic acid-based emulsifiers, sulfuric acid-based emulsifiers, and phosphoric acid-based emulsifiers, and is preferably a sulfuric acid-based emulsifier.

[0093] Examples of fatty acid emulsifiers include sodium octanoate, sodium decanoate, sodium laurate, sodium myristate, sodium palmitate, and sodium stearate.

[0094] Examples of sulfonic acid emulsifiers include sodium hexanesulfonate, sodium octane sulfonate, sodium decane sulfonate, sodium toluenesulfonate, sodium cumenesulfonate, sodium octylbenzenesulfonate, sodium dodecylbenzenesulfonate, ammonium dodecylbenzenesulfonate, sodium naphthalenesulfonate, sodium alkylnaphthalenesulfonate, and sodium alkyldiphenyletherdisulfonate.

[0095] Examples of sulfosuccinic acid emulsifiers include sodium dioctyl sulfosuccinate and sodium dihexyl sulfosuccinate.

[0096] As the sulfate-based emulsifier, sulfate ester salts can be suitably used. Suitable sulfate ester salts include, for example, sodium lauryl sulfate, ammonium lauryl sulfate, sodium myristyl sulfate, sodium laureth sulfate, sodium polyoxyethylene alkyl sulfate, and sodium polyoxyethylene alkylaryl sulfate, and sodium lauryl sulfate is particularly preferred.

[0097] Examples of the phosphoric acid-based emulsifier include sodium lauryl phosphate, potassium lauryl phosphate, and sodium polyoxyalkylene alkyl ether phosphate.

[0098] Examples of the cationic emulsifier include alkyltrimethylammonium chloride, dialkylammonium chloride, and benzylammonium chloride.

[0099] Examples of the nonionic emulsifier include polyoxyalkylene fatty acid esters such as polyoxyethylene stearic acid ester, polyoxyalkylene alkyl ethers such as polyoxyethylene dodecyl ether, polyoxyalkylene alkylphenol ethers such as polyoxyethylene nonylphenyl ether, polyoxyethylene sorbitan alkyl esters, etc. Among these, polyoxyalkylene alkyl ethers and polyoxyalkylene alkylphenol ethers are preferred, and polyoxyethylene alkyl ethers and polyoxyethylene alkylphenol ethers are more preferred.

[0100] These emulsifiers can be used alone or in combination of two or more kinds. The amount used is usually in the range of 0.01 to 10 parts by weight, preferably 0.1 to 5 parts by weight, and more preferably 1 to 3 parts by weight, per 100 parts by weight of the monomer component.

[0101] The monomer component, water, and emulsifier may be mixed according to a conventional method, such as a method of stirring the monomer, emulsifier, and water using a stirrer such as a homogenizer or a disk turbine. The amount of water used is usually in the range of 10 to 750 parts by weight, preferably 50 to 500 parts by weight, and more preferably 100 to 400 parts by weight, based on 100 parts by weight of the monomer component.

[0102] The polymerization catalyst used in the emulsion polymerization step may be any catalyst that is commonly used in emulsion polymerization, and for example, a redox catalyst consisting of a radical generator and a reducing agent can be used.

[0103] Examples of the radical generator include peroxides and azo compounds, and preferably peroxides. As the peroxide, inorganic peroxides and organic peroxides can be used.

[0104] Examples of inorganic peroxides include sodium persulfate, potassium persulfate, hydrogen peroxide, and ammonium persulfate. Among these, potassium persulfate, hydrogen peroxide, and ammonium persulfate are preferred, and potassium persulfate is particularly preferred.

[0105] Examples of organic peroxides include 2,2-di(4,4-di(t-butylperoxy)cyclohexyl)propane, 1-di(t-hexylperoxy)cyclohexane, 1,1-di(t-butylperoxy)cyclohexane, 4,4-di(t-butylperoxy)n-butyl valerate, 2,2-di(t-butylperoxy)butane, t-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, paramenthane hydroperoxide, benzoyl peroxide, and 1,1 ,3,3-Tetraethylbutyl hydroperoxide, t-butylcumyl peroxide, di-t-butyl peroxide, di-t-hexyl peroxide, di(2-t-butylperoxyisopropyl)benzene, dicumyl peroxide, diisobutyryl peroxide, di(3,5,5-trimethylhexanoyl) peroxide, dilauroyl peroxide, disuccinic acid peroxide, dibenzoyl peroxide, di(3-methylbenzoyl) peroxide, benzoyl(3-methylbenzoyl) peroxide, di Isobutyryl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethylhexyl) peroxydicarbonate, di-sec-butyl peroxydicarbonate, 1,1,3,3-tetramethylbutyl peroxyneodecanate, t-hexyl peroxypivalate, t-butyl peroxyneodecanate, t-hexyl peroxypivalate, t-butyl peroxypivalate, 2,5-dimethyl-2,5-di(2-ethylhexanoylperoxy)hexane, 1,1,3,3-tetramethylbutyl peroxyneodecanate, peroxy-2-ethylhexanate, t-hexylperoxy-2-ethylhexanate, t-butylperoxy-3,5,5-trimethylhexanate, t-hexylperoxyisopropyl monocarbonate, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl monocarbonate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, t-hexylperoxybenzoate, t-butylperoxybenzoate, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and among these, diisopropylbenzene hydroperoxide, cumene hydroperoxide, paramenthane hydroperoxide, benzoyl peroxide, and the like are preferred.

[0106] Examples of azo compounds include azobisisoptylonitrile, 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[2-(2-imidazolin-2-yl)propane, 2,2'-azobis(propane-2-carboxamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropanamide], 2,2'-azobis{2-[1-(2-hydroxyethyl)-2-imidazolin-2-yl]propane}, 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane), and 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propanamide}.

[0107] These radical generators can be used alone or in combination of two or more kinds. The amount used is usually in the range of 0.0001 to 5 parts by weight, preferably 0.0005 to 1 part by weight, and more preferably 0.001 to 0.5 parts by weight, per 100 parts by weight of the monomer component.

[0108] The reducing agent can be any reducing agent that is used in a redox catalyst for emulsion polymerization, but in the present invention, it is particularly preferable to use at least two reducing agents in combination. As the at least two reducing agents, for example, a combination of a metal ion compound in a reduced state and another reducing agent is preferable.

[0109] Examples of reduced metal ion compounds include ferrous sulfate, sodium iron hexamethylenediaminetetraacetate, and cuprous naphthenate, and among these, ferrous sulfate is preferred. These reduced metal ion compounds can be used alone or in combination of two or more, and the amount used is usually in the range of 0.000001 to 0.01 parts by weight, preferably 0.00001 to 0.001 parts by weight, and more preferably 0.00005 to 0.0005 parts by weight, relative to 100 parts by weight of the monomer component.

[0110] Examples of reducing agents other than metal ion compounds in a reduced state include ascorbic acid or a salt thereof such as ascorbic acid, sodium ascorbate, or potassium ascorbate; erythorbic acid or a salt thereof such as erythorbic acid, sodium erythorbate, or potassium erythorbate; sulfinic acid salts such as sodium hydroxymethanesulfinate; sulfite salts such as sodium sulfite, potassium sulfite, sodium hydrogensulfite, aldehyde sodium hydrogensulfite, or potassium hydrogensulfite; pyrosulfite salts such as sodium pyrosulfite, potassium pyrosulfite, sodium hydrogensulfite, or potassium pyrosulfite; thiosulfates such as sodium thiosulfate or potassium thiosulfate; phosphorous acid or a salt thereof such as sodium phosphite, potassium phosphite, sodium hydrogen phosphite, or potassium hydrogen phosphite; pyrophosphorous acid or a salt thereof such as pyrophosphorous acid, sodium pyrophosphite, potassium pyrophosphite, sodium hydrogen pyrophosphite, or potassium hydrogen pyrophosphite; sodium formaldehyde sulfoxylate. Among these, ascorbic acid or a salt thereof, sodium formaldehyde sulfoxylate, etc. are preferred, and ascorbic acid or a salt thereof is particularly preferred.

[0111] These reducing agents other than metal ion compounds in a reduced state can be used alone or in combination of two or more kinds, and the amount used is usually in the range of 0.001 to 1 part by weight, preferably 0.005 to 0.5 parts by weight, and more preferably 0.01 to 0.3 parts by weight, per 100 parts by weight of the monomer component.

[0112] A preferred combination of a metal ion compound in a reduced state and another reducing agent is a combination of ferrous sulfate and ascorbic acid or a salt thereof and / or sodium formaldehyde sulfoxylate, more preferably a combination of ferrous sulfate and an ascorbate and / or sodium formaldehyde sulfoxylate, and most preferably a combination of ferrous sulfate and an ascorbate. In this case, the amount of ferrous sulfate used is usually 0.000001 to 0.01 parts by weight, preferably 0.00001 to 0.001 parts by weight, more preferably 0.00005 to 0.0005 parts by weight, relative to 100 parts by weight of the monomer component, and the amount of ascorbic acid or a salt thereof and / or sodium formaldehyde sulfoxylate used is usually 0.001 to 1 part by weight, preferably 0.005 to 0.5 parts by weight, more preferably 0.01 to 0.3 parts by weight, relative to 100 parts by weight of the monomer component.

[0113] The amount of water used in the emulsion polymerization reaction may be only the amount used during emulsification of the monomer components, but is adjusted to be in the range of usually 10 to 1,000 parts by weight, preferably 50 to 500 parts by weight, more preferably 80 to 400 parts by weight, and most preferably 100 to 300 parts by weight, per 100 parts by weight of the monomer components used in the polymerization.

[0114] The emulsion polymerization reaction may be carried out in a conventional manner, and may be any of batch, semi-batch, and continuous. The polymerization temperature and polymerization time are not particularly limited and may be appropriately selected depending on the type of polymerization initiator used. The polymerization temperature is usually in the range of 0 to 100°C, preferably 5 to 80°C, and more preferably 10 to 50°C, and the polymerization time is usually 0.5 to 100 hours, and preferably 1 to 10 hours.

[0115] The polymerization conversion rate of the emulsion polymerization reaction is not limited, but is usually 80% by weight or more, preferably 90% by weight or more, and more preferably 95% by weight or more, which is suitable because the acrylic rubber veil produced has excellent strength characteristics and is free of monomer odor. A polymerization terminator may be used to terminate the polymerization.

[0116] (solidification process) The coagulation step in the method for producing an acrylic rubber sheet of the present invention is characterized in that the obtained emulsion polymerization liquid is added to a stirred coagulation liquid (aqueous solution containing a coagulant) to generate water-containing crumbs.

[0117] The solids concentration of the emulsion polymerization liquid used in the coagulation step is not limited, but is usually adjusted to within the range of 5 to 50% by weight, preferably 10 to 45% by weight, and more preferably 20 to 40% by weight.

[0118] The coagulant used in the coagulation step is not limited, but is usually a metal salt, for example, an alkali metal, a metal salt of Group 2 of the periodic table, or other metal salt, preferably an alkali metal salt or a metal salt of Group 2 of the periodic table, more preferably an alkali metal salt, and particularly preferably a sodium salt.

[0119] Examples of the alkali metal salt used as the coagulant include sodium salts such as sodium chloride, sodium nitrate, and sodium sulfate; potassium salts such as potassium chloride, potassium nitrate, and potassium sulfate; and lithium salts such as lithium chloride, lithium nitrate, and lithium sulfate. Among these, in the present invention, sodium salts such as sodium chloride and sodium sulfate are preferred, and sodium sulfate is particularly preferred.

[0120] Examples of the salts of metals in Group 2 of the periodic table include magnesium chloride, calcium chloride, magnesium nitrate, calcium nitrate, magnesium sulfate, and calcium sulfate, with calcium chloride and magnesium sulfate being preferred.

[0121] Examples of other metal salts include zinc chloride, titanium chloride, manganese chloride, iron chloride, cobalt chloride, nickel chloride, aluminum chloride, tin chloride, zinc nitrate, titanium nitrate, manganese nitrate, iron nitrate, cobalt nitrate, nickel nitrate, aluminum nitrate, tin nitrate, zinc sulfate, titanium sulfate, manganese sulfate, iron sulfate, cobalt sulfate, nickel sulfate, aluminum sulfate, and tin sulfate.

[0122] These coagulants can be used alone or in combination of two or more, and the amount used is usually 0.01 to 100 parts by weight, preferably 0.1 to 50 parts by weight, and more preferably 1 to 30 parts by weight, relative to 100 parts by weight of the monomer component. When the coagulant is in this range, it is preferable because it is possible to sufficiently coagulate the acrylic rubber while highly improving the compression set resistance and water resistance when the acrylic rubber veil is crosslinked.

[0123] The coagulant concentration in the coagulation liquid is usually in the range of 0.1 to 20% by weight, preferably 0.5 to 15% by weight, more preferably 1 to 10% by weight, and particularly preferably 1.5 to 5%, which is suitable because the particle size of the resulting hydrous crumbs can be concentrated uniformly in a specific region.

[0124] The temperature of the coagulation liquid is not limited, but when it is usually 40° C. or higher, preferably 40 to 90° C., more preferably in the range of 50 to 80° C., uniform water-containing crumbs are preferably produced.

[0125] The stirring speed (rotation speed) of the stirred coagulation liquid is represented by the rotation speed of the stirring blade of the stirring device installed in the coagulation bath, and is usually in the range of 100 rpm or more, preferably 200 to 1,000 rpm, more preferably 300 to 900 rpm, and particularly preferably 400 to 800 rpm.

[0126] The rotation speed of the coagulation liquid is preferably such that the coagulation liquid is stirred vigorously to some extent, because the particle size of the generated hydrous crumbs can be made small and uniform. By setting the rotation speed to above the lower limit, the generation of crumbs with excessively large or small particle size can be suppressed, and by setting the rotation speed to below the upper limit, the control of the coagulation reaction becomes easier.

[0127] The peripheral speed of the stirred coagulation liquid is expressed by the linear speed of the outer circumference of the stirring blade of the stirring device, and it is preferable that the coagulation liquid is stirred vigorously to a certain extent because the particle size of the generated water-containing crumbs can be made small and uniform, and is usually 0.5 m / s or more, preferably 1 m / s or more, more preferably 1.5 m / s or more, particularly preferably 2 m / s or more, and most preferably 2.5 m / s or more. On the other hand, the upper limit of the peripheral speed is not limited, but it is usually 50 m / s or less, preferably 30 m / s or less, more preferably 25 m / s or less, and most preferably 20 m / s or less, which is preferable because it makes it easier to control the coagulation reaction.

[0128] By setting the above-mentioned conditions of the coagulation reaction in the coagulation step (contact method, solids concentration of the emulsion polymerization liquid, concentration and temperature of the coagulation liquid, rotation speed and peripheral speed during stirring of the coagulation liquid, etc.) within specific ranges, the shape and diameter of the generated water-containing crumbs are uniform and concentrated, and removal of the emulsifier and coagulant during washing and dehydration is significantly improved, which is preferable.

[0129] The thus-obtained water-containing crumbs preferably satisfy all of the following conditions (a) to (e) when sieved using a JIS classification sieve. The JIS sieve complies with the provisions of the Japanese Industrial Standards (JIS Z 8801-1). (a) The proportion of water-containing crumbs that do not pass through a JIS sieve with a mesh size of 9.5 mm is 10% by weight or less; (b) The proportion of wet crumbs that pass through a JIS sieve with a mesh size of 9.5 mm but not a JIS sieve with a mesh size of 6.7 mm is 30% by weight or less; (c) the proportion of wet crumbs that pass through a JIS sieve with a mesh size of 6.7 mm but do not pass through a JIS sieve with a mesh size of 710 μm is 20% by weight or more; (d) The proportion of water-containing crumbs that pass through a JIS sieve with a mesh size of 710 μm but do not pass through a JIS sieve with a mesh size of 425 μm is 30% by weight or less; and (e) The proportion of moist crumbs passing through a JIS sieve having an opening of 425 μm is 10% by weight or less.

[0130] When the proportion of the generated wet crumbs that do not pass through a JIS sieve (a) with a mesh size of 9.5 mm is 10% by weight or less, preferably 5% by weight or less, and more preferably 1% by weight or less, the washing efficiency of the emulsifier and coagulant can be significantly improved, which is suitable.

[0131] When the proportion of (b) the hydrous crumbs that pass through a JIS sieve with a mesh size of 9.5 mm but not a JIS sieve with a mesh size of 6.7 mm among the hydrous crumbs produced is 30% by weight or less, preferably 20% by weight or less, and more preferably 5% by weight or less, the washing efficiency of the emulsifier and coagulant can be significantly improved, which is suitable.

[0132] When the proportion of (c) the hydrous crumbs that pass through a JIS sieve with a mesh size of 6.7 mm but do not pass through a JIS sieve with a mesh size of 710 μm is 20% by weight or more, preferably 40% by weight or more, more preferably 70% by weight or more, and most preferably 80% by weight or more, the washing efficiency of the emulsifier and coagulant can be significantly improved, which is suitable.

[0133] When the proportion of (d) the hydrous crumbs that pass through a JIS sieve with a mesh size of 710 μm but not a JIS sieve with a mesh size of 425 μm is 30% by weight or less, preferably 20% by weight or less, and more preferably 15% by weight or less, the washing efficiency of the emulsifier and coagulant is significantly improved and the productivity is also high, which is preferable.

[0134] When the proportion of the generated wet crumbs passing through a JIS sieve (e) having an opening of 425 μm is 10% by weight or less, preferably 5% by weight or less, and more preferably 1% by weight or less, the washing efficiency of the emulsifier and coagulant is significantly improved and the productivity is also high, which is preferable.

[0135] In the present invention, the washing efficiency of the emulsifier and coagulant is improved, and it is preferable when the proportion of (f) the hydrous crumbs that pass through a JIS sieve with an opening of 6.7 mm but do not pass through a JIS sieve with an opening of 4.75 mm among the hydrous crumbs produced is usually 40% by weight or less, preferably 10% by weight or less, and more preferably 5% by weight or less.

[0136] In the present invention, it is also preferable that the proportion of (g) the hydrous crumbs that pass through a JIS sieve with a mesh size of 4.75 mm but do not pass through a JIS sieve with a mesh size of 710 μm among the hydrous crumbs produced is usually 40% by weight or more, preferably 60% by weight or more, and more preferably 80% by weight or more, since this significantly improves the removal efficiency of the emulsifier and coagulant during washing and dehydration.

[0137] In the present invention, it is further preferred that the ratio of (h) hydrous crumbs that pass through a JIS sieve with a mesh size of 3.35 mm but do not pass through a JIS sieve with a mesh size of 710 μm among the hydrous crumbs produced is usually 20% by weight or more, preferably 40% by weight or more, more preferably 50% by weight or more, particularly preferably 60% by weight or more, and most preferably 70% by weight or more, since this significantly improves the removal efficiency of the emulsifier and coagulant during washing and dehydration.

[0138] (Cleaning process) The washing step in the method for producing an acrylic rubber veil of the present invention is a step of washing the water-containing crumbs produced as described above with warm water.

[0139] The washing method may be a conventional method, for example, by mixing the produced wet crumbs with a large amount of warm water.

[0140] The amount of warm water used for washing is not particularly limited, but when the amount per one water wash is usually 50 parts by weight or more, preferably 50 to 15,000 parts by weight, more preferably 100 to 10,000 parts by weight, and particularly preferably 150 to 5,000 parts by weight, relative to 100 parts by weight of the monomer component, it is suitable in that the ash content in the acrylic rubber can be effectively reduced.

[0141] The temperature of the hot water used for washing is not limited, but is usually 40° C. or higher, preferably 40 to 100° C., more preferably 50 to 90° C., and most preferably 60 to 80° C., which is suitable for significantly improving the washing efficiency.

[0142] By setting the temperature of the hot water during washing to the above-mentioned lower limit temperature or higher, the emulsifier and coagulant are released from the water-containing crumbs, thereby further improving the washing efficiency.

[0143] The washing time is not limited, but is usually in the range of 1 to 120 minutes, preferably 2 to 60 minutes, and more preferably 3 to 30 minutes.

[0144] The number of washings is not particularly limited, and is usually 1 to 10 times, preferably multiple times, and more preferably 2 to 3 times. From the viewpoint of reducing the amount of residual coagulant in the finally obtained acrylic rubber, it is desirable to wash with water more frequently, but the number of washings can be significantly reduced by specifying the shape and diameter of the wet crumbs and / or setting the washing temperature within the above range.

[0145] (Dehydration process) In the method for producing an acrylic rubber veil of the present invention, it is preferable to provide a dehydration step, prior to the drying step, in which water is squeezed out of the hydrous crumbs after washing using a dehydrator or the like. This reduces the amount of ash that could not be removed in the washing step, and dramatically improves the water resistance of the acrylic rubber veil.

[0146] The dehydrator used in this step is not particularly limited, and for example, a centrifuge, a squeezer, a screw-type extruder, etc. can be used, but a screw-type extruder is particularly suitable because it can highly reduce the moisture content of the water-containing crumb. In a centrifuge, etc., the acrylic rubber, which is sticky, adheres to the wall surface and between the slits, and can usually only be dehydrated to about 45 to 55% by weight. In contrast, a screw-type extruder is suitable because it has a mechanism for forcibly squeezing out the moisture.

[0147] The water content of the dehydrated hydrous crumb is not limited, but is usually in the range of 1 to 50% by weight, preferably 1 to 40% by weight, more preferably 10 to 40% by weight, and more preferably 15 to 35% by weight. By making the water content after dehydration equal to or higher than the lower limit, the dehydration time can be shortened and deterioration of the acrylic rubber can be suppressed, while by making it equal to or lower than the upper limit, the ash content can be sufficiently reduced.

[0148] (drying process) The drying step in the method for producing the acrylic rubber veil of the present invention is a step of drying the hydrous crumbs obtained after the washing step and preferably after further dehydration, for example, by using a screw-type extruder to extrude a dried rubber having a moisture content of less than 1% by weight.

[0149] The temperature of the water-containing crumbs fed into the screw extruder is not limited, but is usually 40°C or higher, preferably 40 to 100°C, more preferably 50 to 90°C, particularly preferably 55 to 85°C, and most preferably 60 to 80°C. When the water-containing crumbs are fed into the screw extruder at this temperature range, it is preferable because the water-containing crumbs, which have a large specific heat of 1.5 to 2.5 KJ / kg·K and are difficult to increase in temperature, such as the acrylic rubber of the present invention, can be reliably dried in the screw extruder. In particular, in the present invention, the water-containing crumbs are dried and melt-kneaded in the screw extruder until they are substantially free of water (water content after dehydration, which will be described later), and are important in the production of acrylic rubber, because this eliminates the gel content of the methyl ethyl ketone insoluble matter that rapidly increases when the polymerization conversion rate of emulsion polymerization is increased.

[0150] The drying temperature (set temperature) in the screw-type extruder is appropriately selected, but a temperature in the range of usually 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C is suitable because it allows efficient drying without causing discoloration or deterioration of the acrylic rubber and reduces the amount of gel in the acrylic rubber veil that is insoluble in methyl ethyl ketone.

[0151] The shape of the dried rubber extruded from the screw-type extruder is not limited, and examples include crumbs, powder, rods, sheets, etc., but among these, a sheet shape is preferred because it allows the production of an acrylic rubber bale that does not entrap air during molding (has a high specific gravity) and has excellent storage stability. The moisture content of the dried rubber is less than 1% by weight, preferably 0.8% by weight or less, and more preferably 0.6% by weight or less.

[0152] (Baling process) The baling step in the method for producing an acrylic rubber bale of the present invention is a step of baling the obtained dry rubber having a moisture content of less than 1% by weight.

[0153] Baling of the dried rubber may be performed according to a conventional method, for example, the dried rubber is placed in a baler and compressed to produce an acrylic rubber bale. The compression pressure is appropriately selected depending on the intended use, but is usually in the range of 0.1 to 15 MPa, preferably 0.5 to 10 MPa, and more preferably 1 to 5 MPa. The compression time is not limited, but is usually in the range of 1 to 60 seconds, preferably 5 to 30 seconds, and more preferably 10 to 20 seconds.

[0154] In the present invention, dry rubber sheets can also be made into bales by laminating them together to form a single unit. Baling by laminating dry rubber sheets is easy to produce and produces bales with fewer air bubbles (high specific gravity), so the resulting acrylic rubber bales have excellent storage stability and are therefore preferred.

[0155] (Dehydration, drying and baling process using a screw-type extruder) In the present invention, the dehydration step and the drying step are preferably carried out continuously using a screw-type extruder equipped with a dehydration barrel having a dehydration slit, a drying barrel for drying under reduced pressure, and a die at the tip, and it is also preferable to carry out a baling step thereafter. An embodiment of this is shown below.

[0156] Draining process In the method for producing the acrylic rubber veil of the present invention, it is preferable to provide a draining step in which free water is separated from the hydrous crumbs after washing using a draining machine before moving from the washing step to the dehydration and drying step, in order to increase the efficiency of dehydration and drying.

[0157] The drainer may be any known type without any limitations, for example, a wire mesh, a screen, an electric sifter, etc., with wire mesh and a screen being preferred.

[0158] The mesh size of the drainer is not limited, but is usually in the range of 0.01 to 5 mm, preferably 0.1 to 1 mm, and more preferably 0.2 to 0.6 mm, which is suitable since it allows efficient draining with little loss of water-containing crumb.

[0159] The moisture content of the hydrous crumbs after draining, i.e., the moisture content of the hydrous crumbs fed into the dehydration, drying and molding process, is not limited, but is usually in the range of 50 to 80% by weight, preferably 50 to 70% by weight, and more preferably 50 to 60% by weight.

[0160] The temperature of the hydrous crumbs after draining, i.e., the temperature of the hydrous crumbs fed into the dehydration, drying and molding process, is not limited, but is usually 40°C or higher, preferably 40 to 95°C, more preferably 50 to 90°C, particularly preferably 55 to 85°C, and most preferably in the range of 60 to 80°C.

[0161] Dehydration and drying in the dehydration barrel The dehydration of the hydrous crumb is carried out in a dehydration barrel having a dehydration slit provided in the screw-type extruder. The opening of the dehydration slit may be appropriately selected depending on the conditions of use, but it is usually 0.1 to 1 mm, preferably 0.2 to 0.6 mm, which is suitable because the loss of the hydrous crumb is small and the hydrous crumb can be efficiently dehydrated.

[0162] The number of dehydration barrels in the screw extruder is not limited, but it is generally suitable to have more than one, preferably 2 to 10, and more preferably 3 to 6, so that the viscous acrylic rubber can be dehydrated efficiently.

[0163] There are two ways to remove water from the wet crumb in the dewatering barrel: in liquid form (wastewater) through the dewatering slit, and in vapor form (exhaust steam). In the present invention, however, drainage is distinguished as dewatering, and exhaust steam is distinguished as preliminary drying.

[0164] When dehydration is performed using a screw-type extruder equipped with a plurality of dehydration barrels, it is preferable to combine drainage and exhaust steam to efficiently realize drainage (dehydration) and reduction of the moisture content of the viscous acrylic rubber. Whether each barrel of a screw-type extruder equipped with three or more dehydration barrels is a drainage type dehydration barrel or an exhaust steam type dehydration barrel may be appropriately selected according to the purpose of use. Usually, when the ash content in the produced acrylic rubber is reduced, the number of drainage type dehydration barrels is increased, for example, when there are three dehydration barrels, two drainage type dehydration barrels are selected, and when there are four dehydration barrels, three drainage type dehydration barrels are selected, etc.

[0165] The set temperature of the dehydration barrel is appropriately selected depending on the type of acrylic rubber, the ash content, the water content, the operating conditions, etc., but is usually in the range of 60 to 150° C., preferably 70 to 140° C., and more preferably 80 to 130° C. The set temperature of the drainage type dehydration barrel for dehydrating in a drainage state is usually 60 to 120° C., preferably 70 to 110° C., and more preferably 80 to 100° C., and the set temperature of the exhaust steam type dehydration barrel for drying in an exhaust steam state is usually in the range of 100 to 150° C., preferably 105 to 140° C., and more preferably 110 to 130° C.

[0166] The moisture content after dehydration in a drainage type dehydration barrel that squeezes out moisture from the wet crumb is not limited, but is usually 1 to 45% by weight, preferably 1 to 40% by weight, more preferably 5 to 35% by weight, and particularly preferably 10 to 35% by weight, which is suitable because it provides a high balance between productivity and ash removal efficiency.

[0167] When dehydration of sticky acrylic rubber is performed using a centrifuge or the like, the acrylic rubber adheres to the dehydration slits and is hardly dehydrated, and the moisture content is reduced only to about 45 to 55% by weight. On the other hand, in the present invention, by using a screw-type extruder having a dehydration slit and forcibly squeezed by a screw, it is possible to reduce the moisture content to the above range.

[0168] In the case where a drainage type dehydration barrel and a steam exhaust type dehydration barrel are provided, the moisture content after dehydration in the drainage type dehydration barrel is usually 5 to 45% by weight, preferably 10 to 40% by weight, and more preferably 15 to 35% by weight, and the moisture content after preliminary drying in the steam exhaust type dehydration barrel is usually 1 to 30% by weight, preferably 3 to 20% by weight, and more preferably 5 to 15% by weight.

[0169] By setting the water content after dehydration to above the above lower limit, the dehydration time can be shortened and deterioration of the acrylic rubber can be suppressed, whereas by setting it to below the above upper limit, the ash content can be sufficiently reduced.

[0170] Drying in the drying barrel The wet crumbs that have been dehydrated and dried in the dehydration barrel are further dried in the drying barrel under reduced pressure.

[0171] The degree of reduced pressure in the drying barrel may be appropriately selected, but is usually 1 to 50 kPa, preferably 2 to 30 kPa, and more preferably 3 to 20 kPa, which is suitable for efficiently drying the water-containing crumbs.

[0172] The set temperature of the drying barrel may be appropriately selected, but is usually suitable to be in the range of 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C, since this allows efficient drying without causing scorching or deterioration of the acrylic rubber and reduces the amount of gel of the acrylic rubber that is insoluble in methyl ethyl ketone.

[0173] The number of drying barrels in the screw extruder is not limited, but is usually more than one, preferably 2 to 10, more preferably 3 to 8. When there are more than one drying barrels, the degree of reduced pressure may be similar for all drying barrels or may be different. When there are more than one drying barrels, the set temperature may be similar for all drying barrels or may be different, but it is preferable to set the temperature of the discharge part (closer to the die) higher than the temperature of the introduction part (closer to the dehydration barrel) because this can increase the drying efficiency.

[0174] The water content of the dried rubber after drying is usually less than 1% by weight, preferably 0.8% by weight or less, more preferably 0.6% by weight or less.

[0175] In the present invention, by melt kneading the acrylic rubber in the drying barrel in a state substantially free of moisture, the amount of gel of the methyl ethyl ketone insoluble matter which has rapidly increased during emulsion polymerization disappears, and the processability of the acrylic rubber veil during Banbury kneading, etc. is advantageously improved significantly.

[0176] Shape of acrylic rubber (die part) The acrylic rubber dehydrated and dried in the screw sections of the dehydrating barrel and the drying barrel is sent to a screw-free straightening die section provided at the tip of the screw extruder. A breaker plate or a wire mesh may or may not be provided between the screw section and the die section.

[0177] The acrylic rubber extruded from the die portion of the screw-type extruder can be obtained in a variety of shapes, such as powder, pellets, columns, round rods, and sheets, depending on the shape of the die nozzle. However, extruding into a sheet shape using a substantially rectangular die is preferred, as this reduces the entrapment of air during extrusion and allows for the production of a dried rubber with a high specific gravity and excellent storage stability.

[0178] The resin pressure in the die section is not limited, but is usually in the range of 0.1 to 10 MPa, preferably 0.5 to 5 MPa, and more preferably 1 to 3 MPa, which is suitable for minimizing air entrapment and providing excellent productivity.

[0179] Screw type extruder and operating conditions The screw length (L) of the screw type extruder used in the present invention may be appropriately selected depending on the purpose of use, but is usually in the range of 3,000 to 15,000 mm, preferably 4,000 to 10,000 mm, and more preferably 4,500 to 8,000 mm.

[0180] The screw diameter (D) of the screw extruder may be appropriately selected depending on the purpose of use, but is usually in the range of 50 to 250 mm, preferably 100 to 200 mm, and more preferably 120 to 160 mm. The ratio (L / D) of the screw length (L) to the screw diameter (D) of the screw extruder is not limited, but is usually suitable when it is in the range of 10 to 100, preferably 20 to 80, more preferably 30 to 60, and particularly preferably 40 to 50, since the moisture content can be reduced to less than 1% by weight without causing a decrease in the molecular weight of the dried rubber or discoloration.

[0181] In the present invention, the rotation speed (N) of the screw-type extruder may be appropriately selected depending on various conditions, but a rotation speed of usually 10 to 1,000 rpm, preferably 50 to 750 rpm, more preferably 100 to 500 rpm, and most preferably 120 to 300 rpm is suitable because it allows the water content of the acrylic rubber and the amount of gel of the methyl ethyl ketone-insoluble matter to be efficiently reduced.

[0182] The extrusion rate (Q) of the screw extruder is not limited, but is usually in the range of 100 to 1,500 kg / hr, preferably 300 to 1,200 kg / hr, more preferably 400 to 1,000 kg / hr, and most preferably 500 to 800 kg / hr.

[0183] The ratio (Q / N) of the extrusion rate (Q) to the rotation speed (N) of the screw-type extruder in the present invention is not limited, but is usually suitable to be in the range of 2 to 10, preferably 3 to 8, and more preferably 4 to 6, since this range provides a high balance between the quality, including the strength properties, of the obtained acrylic rubber sheet and the production productivity.

[0184] Dry rubber As described above, the shape of the dried rubber extruded from the screw-type extruder is not limited, and can be, for example, in the form of crumbs, powder, pellets, rods, sheets, etc., with the sheet shape being particularly preferred.

[0185] The temperature of the dried rubber extruded from the screw extruder is not limited, but is usually in the range of 100 to 200°C, preferably 110 to 180°C, and more preferably 120 to 160°C.

[0186] The moisture content of the dry rubber extruded from the screw-type extruder is less than 1% by weight, preferably 0.8% by weight or less, and more preferably 0.6% by weight or less.

[0187] Baling process The baling step after the dehydration and drying step using a screw extruder is a step of baling the extruded dry rubber. Baling of the dry rubber may be performed according to a conventional method, for example, the dry rubber may be put into a baler and compressed to produce the rubber. The compression pressure of the baler may be appropriately selected depending on the intended use, but is usually in the range of 0.1 to 15 MPa, preferably 0.5 to 10 MPa, and more preferably 1 to 5 MPa. The compression temperature is not limited, but is usually in the range of 10 to 80°C, preferably 20 to 60°C, and more preferably 30 to 60°C. The compression time may be appropriately selected depending on the intended use, but is usually in the range of 1 to 100 seconds, preferably 2 to 50 seconds, and more preferably 5 to 25 seconds.

[0188] In the present invention, it is preferable to extrude the dried rubber in sheet form from a screw extruder in the above-mentioned dehydration and drying step, cut it as necessary, and stack it to form a bale. Forming a bale by stacking the dried rubber in sheet form is easy to produce, and furthermore, it produces a bale with few air bubbles (high specific gravity), which is preferable because it has excellent storage stability.

[0189] The following describes an embodiment in which a sheet of dry rubber is extruded from a screw extruder and then the sheets are laminated to form a bale.

[0190] The thickness of the sheet-like dry rubber extruded from the screw extruder is not particularly limited, but is preferably in the range of usually 1 to 40 mm, preferably 2 to 35 mm, more preferably 3 to 30 mm, and most preferably 5 to 25 mm, which is excellent in workability and productivity. In particular, when the thermal conductivity of the sheet-like dry rubber is as low as 0.15 to 0.35 W / mK and the cooling efficiency is increased to significantly improve the productivity, the thickness of the sheet-like dry rubber is usually in the range of 1 to 30 mm, preferably 2 to 25 mm, more preferably 3 to 15 mm, and particularly preferably 4 to 12 mm.

[0191] The width of the sheet-like dry rubber extruded from the screw extruder is appropriately selected depending on the intended use, but is usually in the range of 300 to 1,200 mm, preferably 400 to 1,000 mm, and more preferably 500 to 800 mm.

[0192] The temperature of the dry rubber sheet extruded from the screw extruder is not limited, but is usually in the range of 100 to 200°C, preferably 110 to 180°C, and more preferably 120 to 160°C.

[0193] The complex viscosity at 100°C of the dry rubber sheet extruded from the screw extruder ([η]100°C) is not limited, but is usually in the range of 1,500 to 6,000 Pa·s, preferably 2,000 to 5,000 Pa·s, more preferably 2,500 to 4,000 Pa·s, and most preferably 2,500 to 3,500 Pa·s, which is suitable since it provides a high balance between extrudability as a sheet and shape retention. That is, by setting the complex viscosity ([η]100°C) to be equal to or higher than the above lower limit, the extrudability can be made superior, and by setting it to be equal to or lower than the above upper limit, deformation or breakage of the dry rubber sheet can be suppressed.

[0194] In the present invention, the dry rubber sheet extruded from the screw extruder is cut into pieces of an appropriate size, and then a plurality of cut dry rubber sheets are laminated and integrated to form a bale. This method is preferred because it entraps only a small amount of air and the resulting acrylic rubber bale has excellent storage stability.

[0195] The method for cutting the dry rubber sheet is not particularly limited, but since the acrylic rubber in the acrylic rubber veil of the present invention is highly adhesive, it is preferable to cut the dry rubber sheet after cooling it in order to cut it continuously without drawing air in. The cutting temperature for the dry rubber sheet is not limited, but a cutting temperature of usually 60° C. or less, preferably 55° C. or less, more preferably 50° C. or less is suitable as it provides a high balance between cuttability and productivity.

[0196] The complex viscosity of the dry rubber sheet at 60°C ([η]60°C) is not limited, but is usually 15,000 Pa·s or less, preferably 2,000 to 10,000 Pa·s, more preferably 2,500 to 7,000 Pa·s, and most preferably in the range of 2,700 to 5,500 Pa·s, which is suitable because it allows continuous cutting without entraining air.

[0197] The ratio ([η]100°C / [η]60°C) of the complex viscosity of the dry rubber sheet at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is not limited, but is usually 0.5 or more, preferably 0.5 to 0.98, more preferably 0.6 to 0.95, and most preferably 0.75 to 0.93, which is suitable because it reduces air entrapment and provides a high balance between cutting and productivity.

[0198] The cooling method for the dry rubber sheet is not particularly limited, and the sheet may be left to cool at room temperature. However, since the thermal conductivity of the dry rubber sheet is very low at 0.15 to 0.35 W / mK, forced cooling such as air cooling using blowing air or cooling, water spraying by spraying water, or immersion in water is preferred in order to increase productivity, and air cooling using blowing air or cooling is particularly preferred.

[0199] In the air-cooling method of the sheet-like dry rubber, for example, a method can be adopted in which the sheet-like dry rubber is extruded from a screw-type extruder onto a conveyer such as a belt conveyer, and conveyed and cooled while being blown with cold air. The temperature of the cold air is not limited, but is usually in the range of 0 to 25°C, preferably 5 to 25°C, and more preferably 10 to 20°C. The length to be cooled is not limited, but is usually in the range of 5 to 500m, preferably 10 to 200m, and more preferably 20 to 100m. The cooling speed of the sheet-like dry rubber is not particularly limited, but is preferably usually 50°C / hr or more, more preferably 100°C / hr or more, and more preferably 150°C / hr or more, since cutting becomes particularly easy.

[0200] The cutting length of the dry rubber sheet is not particularly limited and may be appropriately selected according to the size of the acrylic rubber bale to be produced, but is usually in the range of 100 to 800 mm, preferably 200 to 500 mm, and more preferably 250 to 450 mm.

[0201] The cut dry rubber sheets are laminated to form a bale. The lamination temperature for the dry rubber sheets is not limited, but is usually 30° C. or higher, preferably 35° C. or higher, and more preferably 40° C. or higher, which is suitable for allowing air entrapped during lamination to escape. The number of layers may be appropriately selected depending on the size or weight of the acrylic rubber bale.

[0202] The acrylic rubber veil of the present invention thus obtained is superior in handling and storage stability to crumb-like acrylic rubber. When producing a rubber mixture using the acrylic rubber veil, the acrylic rubber veil can be put into a mixer such as a Banbury mixer or roll, either as is or after cutting into the required amount.

[0203] <Rubber mixture> The rubber mixture of the present invention is characterized by being obtained by mixing the above-mentioned acrylic rubber veil with a filler and a crosslinking agent.

[0204] The filler to be added to the rubber mixture is not limited, but may be, for example, a reinforcing filler or a non-reinforcing filler, with a reinforcing filler being preferred.

[0205] Examples of such reinforcing fillers include carbon blacks such as furnace black, acetylene black, thermal black, channel black, and graphite; silicas such as wet silica, dry silica, and colloidal silica; etc. Examples of non-reinforcing fillers include quartz powder, diatomaceous earth, zinc oxide, basic magnesium carbonate, activated calcium carbonate, magnesium silicate, aluminum silicate, titanium dioxide, talc, aluminum sulfate, calcium sulfate, barium sulfate, etc.

[0206] These fillers can be used alone or in combination of two or more kinds. The amount of the filler to be added is not particularly limited, but is usually in the range of 1 to 200 parts by weight, preferably 10 to 150 parts by weight, and more preferably 20 to 100 parts by weight, per 100 parts by weight of the acrylic rubber veil.

[0207] The crosslinking agent to be contained in the rubber mixture may be appropriately selected according to the type of reactive group contained in the acrylic rubber constituting the acrylic rubber veil and the purpose, but is not limited as long as it can crosslink the acrylic rubber veil, and for example, conventionally known crosslinking agents such as polyamine compounds such as diamine compounds and carbonates thereof, sulfur compounds, sulfur donors, triazine thiol compounds, polyepoxy compounds, organic ammonium carboxylate salts, organic peroxides, polycarboxylic acids, quaternary onium salts, imidazole compounds, isocyanuric acid compounds, organic peroxides, and triazine compounds can be used. Among these, polyamine compounds, ammonium carboxylate salts, metal dithiocarbamate salts, and triazine thiol compounds are preferred, and hexamethylenediamine carbamate, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, ammonium benzoate, and 2,4,6-trimercapto-1,3,5-triazine are particularly preferred.

[0208] When the acrylic rubber veil used is composed of a carboxyl group-containing acrylic rubber, it is preferable to use a polyamine compound and / or a carbonate thereof as the crosslinking agent. Specific examples of such polyvalent amine compounds include aliphatic polyvalent amine compounds such as hexamethylenediamine, hexamethylenediamine carbamate, and N,N'-dicinnamylidene-1,6-hexanediamine; and aromatic polyvalent amine compounds such as 4,4'-methylenedianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-(m-phenylenediisopropylidene)dianiline, 4,4'-(p-phenylenediisopropylidene)dianiline, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminobenzanilide, 4,4'-bis(4-aminophenoxy)biphenyl, m-xylylenediamine, p-xylylenediamine, and 1,3,5-benzenetriamine. Among these, hexamethylenediamine carbamate, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, and the like are preferred.

[0209] When the acrylic rubber veil used is composed of an epoxy group-containing acrylic rubber, examples of the crosslinking agent that can be used include aliphatic polyamine compounds, such as hexamethylenediamine and hexamethylenediamine carbamate, and carbonates thereof; aromatic polyamine compounds, such as 4,4'-methylenedianiline; ammonium carboxylate salts, such as ammonium benzoate and ammonium adipate; metal dithiocarbamate salts, such as zinc dimethyldithiocarbamate; polycarboxylic acids, such as tetradecanedioic acid; quaternary onium salts, such as cetyltrimethylammonium bromide; imidazole compounds, such as 2-methylimidazole; and isocyanuric acid compounds, such as ammonium isocyanurate. Of these, ammonium carboxylate salts and metal dithiocarbamate salts are preferred, with ammonium benzoate being more preferred.

[0210] When the acrylic rubber veil used is composed of a halogen-containing acrylic rubber, it is preferable to use sulfur, a sulfur donor, or a triazine thiol compound as a crosslinking agent. Examples of sulfur donors include dipentamethylene thiuram hexasulfide and triethyl thiuram disulfide. Examples of triazine compounds include 6-trimercapto-s-triazine, 2-anilino-4,6-dithiol-s-triazine, 1-dibutylamino-3,5-dimercaptotriazine, 2-dibutylamino-4,6-dithiol-s-triazine, 1-phenylamino-3,5-dimercaptotriazine, 2,4,6-trimercapto-1,3,5-triazine, and 1-hexylamino-3,5-dimercaptotriazine, and among these, 2,4,6-trimercapto-1,3,5-triazine is preferred.

[0211] These crosslinking agents can be used alone or in combination of two or more, and the amount of the crosslinking agent is usually 0.001 to 20 parts by weight, preferably 0.1 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, per 100 parts by weight of the acrylic rubber veil. By setting the amount of the crosslinking agent within this range, it is possible to obtain excellent mechanical strength as a crosslinked rubber product while ensuring sufficient rubber elasticity, which is preferable.

[0212] The rubber mixture of the present invention may contain other rubber components in addition to the above-mentioned acrylic rubber veil, if necessary.

[0213] Other rubber components used as necessary are not particularly limited, and examples thereof include natural rubber, polybutadiene rubber, polyisoprene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, silicone rubber, fluororubber, olefin-based elastomer, styrene-based elastomer, vinyl chloride-based elastomer, polyester-based elastomer, polyamide-based elastomer, polyurethane-based elastomer, polysiloxane-based elastomer, etc. The shape of the other rubber components is not limited, and may be, for example, any of powder, crumb, sheet, veil, etc.

[0214] These other rubber components may be used alone or in combination of two or more. The amount of these other rubber components used is appropriately selected within a range that does not impair the effects of the present invention.

[0215] The rubber mixture of the present invention may contain an antioxidant as required. Examples of the antioxidant include, but are not limited to, 2,6-di-t-butyl-4-methylphenol, 2,6-di-t-butylphenol, butylhydroxyanisole, 2,6-di-t-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methyl-benzyl-p-cresol), 4,4'-methylenebis( Other phenols such as 2,6-di-t-butylphenol), 2,2'-methylene-bis(4-methyl-6-t-butylphenol), 2,4-bis[(octylthio)methyl]-6-methylphenol, 2,2'-thiobis-(4-methyl-6-t-butylphenol), 4,4'-thiobis-(6-t-butyl-o-cresol), 2,6-di-t-butyl-4-(4,6-bis(octylthio)-1,3,5-triazin-2-ylamino)phenol, Phenolic antioxidants; phosphorous ester antioxidants such as tris(nonylphenyl)phosphite, diphenylisodecylphosphite, and tetraphenyldipropylene glycol diphosphite; sulfur ester antioxidants such as dilauryl thiodipropionate; phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamido)-diphenylamine, and 4,4'-(α,α-dimethylbenzyl)diphenylamine. Examples of such antioxidants include amine-based antioxidants such as butyl aldehyde, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, and butyraldehyde-aniline condensates; imidazole-based antioxidants such as 2-mercaptobenzimidazole; quinoline-based antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline; and hydroquinone-based antioxidants such as 2,5-di-(t-amyl)hydroquinone. Among these, amine-based antioxidants are particularly preferred.

[0216] These antioxidants can be used alone or in combination of two or more. The amount of the antioxidant to be added is in the range of 0.01 to 15 parts by weight, preferably 0.1 to 10 parts by weight, and more preferably 1 to 5 parts by weight, per 100 parts by weight of the acrylic rubber veil.

[0217] The rubber mixture of the present invention contains the acrylic rubber veil of the present invention, a filler, a crosslinking agent, and if necessary, other rubber components and antiaging agents, and further, if necessary, other additives normally used in the technical field can be arbitrarily blended, such as crosslinking aids, crosslinking accelerators, crosslinking retarders, silane coupling agents, plasticizers, processing aids, lubricants, pigments, colorants, antistatic agents, foaming agents, etc. These other compounding agents can be used alone or in combination of two or more, and the blending amounts are appropriately selected within the range that does not impair the effects of the present invention.

[0218] <Method of manufacturing rubber mixture> The method for producing the rubber mixture of the present invention includes a method in which the acrylic rubber veil of the present invention is mixed with a filler, a crosslinking agent, and other compounding ingredients that may be contained as necessary, and any means conventionally used in the field of rubber processing can be used for mixing, such as an open roll, a Banbury mixer, various kneaders, etc. That is, the acrylic rubber veil can be directly mixed with the filler, the crosslinking agent, etc., using these mixers, and preferably mixed by direct kneading.

[0219] In this case, the acrylic rubber veil of the present invention may be used as is, or may be divided (cut, etc.) before use.

[0220] The mixing procedure of each component is not limited, but for example, two-stage mixing is preferred in which components that do not easily react or decompose when heated are thoroughly mixed, and then components that easily react or decompose when heated, such as crosslinking agents, are mixed for a short time at a temperature at which they do not react or decompose. Specifically, it is preferred to mix the acrylic rubber veil and filler in the first stage, and then mix the crosslinking agent in the second stage. Other rubber components and antioxidants are usually mixed in the first stage, the crosslinking accelerator in the second stage, and other compounding agents may be selected as appropriate.

[0221] The Mooney viscosity (ML1+4, 100° C.; compound Mooney) of the rubber mixture of the present invention thus obtained is not limited, but is usually in the range of 10-150, preferably 20-100, more preferably 25-80.

[0222] <Rubber cross-linked products> The cross-linked rubber product of the present invention is obtained by cross-linking the above-mentioned rubber mixture. The cross-linked rubber product of the present invention can be produced by using the rubber mixture of the present invention, molding it into a desired shape using a molding machine such as an extruder, an injection molding machine, a compressor, or a roll, heating it to cause a cross-linking reaction, and fixing the shape as a cross-linked rubber product. In this case, cross-linking may be performed after molding in advance, or may be performed simultaneously with molding. The molding temperature is usually 10 to 200°C, preferably 25 to 150°C. The cross-linking temperature is usually 100 to 250°C, preferably 130 to 220°C, more preferably 150 to 200°C, and the cross-linking time is usually 0.1 minutes to 10 hours, preferably 1 minute to 5 hours. As the heating method, a method used for cross-linking rubber, such as press heating, steam heating, oven heating, and hot air heating, may be appropriately selected.

[0223] The cross-linked rubber of the present invention may be further heated to carry out secondary cross-linking depending on the shape, size, etc. of the cross-linked rubber. The time for secondary cross-linking varies depending on the heating method, cross-linking temperature, shape, etc., but is preferably carried out for 1 to 48 hours. The heating method and heating temperature may be appropriately selected.

[0224] The cross-linked rubber of the present invention has excellent water resistance while maintaining basic rubber properties such as tensile strength, elongation, and hardness.

[0225] Taking advantage of the above-mentioned excellent properties, the cross-linked rubber product of the present invention can be suitably used for, for example, sealing materials such as O-rings, packings, diaphragms, oil seals, shaft seals, bearing sheaths, mechanical seals, well head seals, seals for electric and electronic devices, and seals for air compressors; various gaskets such as a rocker cover gasket attached to the joint between a cylinder block and a cylinder head, an oil pan gasket attached to the joint between an oil pan and a cylinder head or a transmission case, a gasket for a fuel cell separator attached between a pair of housings sandwiching a unit cell having a positive electrode, an electrolyte plate, and a negative electrode, and a gasket for the top cover of a hard disk drive; cushioning materials, vibration-proofing materials; wire covering materials; industrial belts; tubes and hoses; sheets; and the like.

[0226] The cross-linked rubber product of the present invention can also be suitably used as an extrusion molded product and a mold cross-linked product for automotive applications, for example, various hoses such as fuel oil hoses around fuel tanks, such as fuel hoses, filler neck hoses, vent hoses, paper hoses and oil hoses, air hoses such as turbo air hoses and mission control hoses, radiator hoses, heater hoses, brake hoses and air conditioner hoses.

[0227] <Device configuration used in the production of acrylic rubber veils> Next, the configuration of the equipment used in the production of the acrylic rubber veil according to one embodiment of the present invention will be described. Fig. 1 is a diagram showing a schematic diagram of an example of an acrylic rubber production system having an equipment configuration used in the production of the acrylic rubber veil according to one embodiment of the present invention. For example, the acrylic rubber production system 1 shown in Fig. 1 can be used to produce the acrylic rubber according to the present invention.

[0228] The acrylic rubber production system 1 shown in FIG. 1 is composed of an emulsion polymerization reactor, a coagulation device 3, a washing device 4, a draining machine 43, a screw-type extruder 5, a cooling device 6, and a baling device 7, all of which are not shown.

[0229] The emulsion polymerization reactor is configured to carry out the treatment related to the emulsion polymerization step described above. Although not shown in FIG. 1, this emulsion polymerization reactor has, for example, a polymerization reaction tank, a temperature control unit for controlling the reaction temperature, and a stirring device equipped with a motor and a stirring blade. In the emulsion polymerization reactor, the monomer components for forming the acrylic rubber are mixed with water and an emulsifier, emulsified while being appropriately stirred with a stirrer, and emulsion-polymerized in the presence of a polymerization catalyst to obtain an emulsion polymerization liquid. The emulsion polymerization reactor may be any of a batch type, a semi-batch type, and a continuous type, and may be any of a tank type reactor and a tubular type reactor.

[0230] The solidification device 3 shown in Fig. 1 is configured to perform the above-mentioned solidification process. As shown in Fig. 1, the solidification device 3 has, for example, a stirring tank 30, a heating unit 31 for heating the inside of the stirring tank 30, a temperature control unit (not shown) for controlling the temperature inside the stirring tank 30, a stirring device 34 equipped with a motor 32 and a stirring blade 33, and a drive control unit (not shown) for controlling the number of revolutions and the rotation speed of the stirring blade 33. In the solidification device 3, the emulsion polymerization liquid obtained in the emulsion polymerization reactor is brought into contact with a coagulation liquid as a coagulant and solidified to produce water-containing crumbs.

[0231] In the coagulation device 3, for example, the emulsion polymerization liquid is brought into contact with the coagulation liquid by adding the coagulation liquid to an aqueous magnesium salt solution that is being stirred. That is, the stirring tank 30 of the coagulation device 3 is filled with the coagulation liquid, and the emulsion polymerization liquid is added to and brought into contact with the coagulation liquid to coagulate the emulsion polymerization liquid, thereby generating water-containing crumbs.

[0232] The heating unit 31 of the solidification device 3 is configured to heat the solidification liquid filled in the stirring tank 30. The temperature control unit of the solidification device 3 is configured to control the heating operation by the heating unit 31 while monitoring the temperature in the stirring tank 30 measured by a thermometer, thereby controlling the temperature in the stirring tank 30. The temperature of the solidification liquid in the stirring tank 30 is controlled by the temperature control unit to be usually 40°C or higher, preferably in the range of 40 to 90°C, and more preferably 50 to 80°C.

[0233] The agitator 34 of the solidification device 3 is configured to agitate the solidification liquid filled in the agitation tank 30. Specifically, the agitator 34 includes a motor 32 that generates rotational power, and an agitator blade 33 that spreads in a direction perpendicular to the rotation axis of the motor 32. The agitator blade 33 can cause the solidification liquid filled in the agitation tank 30 to flow by rotating around the rotation axis by the rotational power of the motor 32. The shape, size, and number of the agitator blades 33 to be installed are not particularly limited.

[0234] The drive control unit of the solidification device 3 is configured to control the rotation drive of the motor 32 of the agitation device 34 to set the number of rotations and the rotation speed of the agitation blade 33 of the agitation device 34 to a predetermined value. The rotation of the agitation blade 33 is controlled by the drive control unit so that the agitation speed of the solidification liquid is, for example, usually 100 rpm or more, preferably 200 to 1,000 rpm, more preferably 300 to 900 rpm, and particularly preferably 400 to 800 rpm. The rotation of the agitation blade 33 is controlled by the drive control unit so that the peripheral speed of the solidification liquid is usually 0.5 m / s or more, preferably 1 m / s or more, more preferably 1.5 m / s or more, particularly preferably 2 m / s or more, and most preferably 2.5 m / s or more. Furthermore, the rotation of the agitation blade 33 is controlled by the drive control unit so that the upper limit of the peripheral speed of the solidification liquid is usually 50 m / s or less, preferably 30 m / s or less, more preferably 25 m / s or less, and most preferably 20 m / s or less.

[0235] The washing device 4 shown in Fig. 1 is configured to perform the treatment related to the washing step described above. As shown in Fig. 1, the washing device 4 has, for example, a washing tank 40, a heating unit 41 that heats the inside of the washing tank 40, and a temperature control unit (not shown) that controls the temperature inside the washing tank 40. In the washing device 4, the water-containing crumbs generated in the solidifying device 3 are mixed with a large amount of water and washed, thereby effectively reducing the amount of ash in the finally obtained acrylic rubber veil.

[0236] The heating unit 41 of the cleaning device 4 is configured to heat the inside of the cleaning tank 40. The temperature control unit of the cleaning device 4 is configured to control the heating operation by the heating unit 41 while monitoring the temperature inside the cleaning tank 40 measured by a thermometer, thereby controlling the temperature inside the cleaning tank 40. As described above, the temperature of the cleaning water inside the cleaning tank 40 is controlled to be usually in the range of 40°C or higher, preferably 40 to 100°C, more preferably 50 to 90°C, and most preferably 60 to 80°C.

[0237] The water-containing crumb washed in the washing device 4 is supplied to a screw-type extruder 5 which performs a dehydration step and a drying step. At this time, the water-containing crumb after washing is preferably supplied to the screw-type extruder 5 through a drainer 43 capable of separating free water. For the drainer 43, for example, a wire net, a screen, an electric sieve, or the like can be used.

[0238] In addition, when the washed wet crumbs are supplied to the screw-type extruder 5, the temperature of the wet crumbs is preferably 40° C. or higher, more preferably 60° C. or higher. For example, the temperature of the water used for washing in the washing device 4 may be set to 60° C. or higher (e.g., 70° C.) so that the temperature of the wet crumbs when supplied to the screw-type extruder 5 can be maintained at 60° C. or higher, or the wet crumbs may be heated to a temperature of 40° C. or higher, preferably 60° C. or higher, when conveyed from the washing device 4 to the screw-type extruder 5. This makes it possible to effectively perform the subsequent dehydration and drying steps, and to significantly reduce the moisture content of the finally obtained dried rubber.

[0239] The screw-type extruder 5 shown in Fig. 1 is configured to perform the processes related to the dehydration step and the drying step described above. Although the screw-type extruder 5 is shown in Fig. 1 as a suitable example, a centrifuge or a squeezer may be used as a dehydrator that performs the process related to the dehydration step, and a hot air dryer, a reduced pressure dryer, an expander dryer, a kneader dryer, etc. may be used as a dryer that performs the process related to the drying step.

[0240] The screw-type extruder 5 is configured to mold the dried rubber obtained through the dehydration process and the drying process into a predetermined shape and discharge it. Specifically, the screw-type extruder 5 is equipped with a dehydration barrel section 53 having a function as a dehydrator for dehydrating the wet crumbs washed in the washing device 4, and a drying barrel section 54 having a function as a dryer for drying the wet crumbs, and further equipped with a die 59 downstream of the screw-type extruder 5 having a molding function for molding the wet crumbs.

[0241] Hereinafter, the configuration of the screw-type extruder 5 will be described with reference to Fig. 2. Fig. 2 shows the configuration of a specific example suitable for the screw-type extruder 5 shown in Fig. 1. By using this screw-type extruder 5, the above-mentioned dehydration and drying process can be suitably carried out.

[0242] The screw-type extruder 5 shown in Fig. 2 is a twin-screw type extrusion dryer having a pair of screws (not shown) in a barrel unit 51. The screw-type extruder 5 has a drive unit 50 that rotates and drives the pair of screws in the barrel unit 51. The drive unit 50 is attached to the upstream end (left end in Fig. 2) of the barrel unit 51. The screw-type extruder 5 also has a die 59 at the downstream end (right end in Fig. 2) of the barrel unit 51.

[0243] The barrel unit 51 has, from the upstream side to the downstream side (from the left side to the right side in FIG. 2), a supply barrel section 52, a dewatering barrel section 53, and a drying barrel section .

[0244] The supply barrel section 52 is made up of two supply barrels, that is, a first supply barrel 52a and a second supply barrel 52b.

[0245] The dehydration barrel section 53 is made up of three dehydration barrels, that is, a first dehydration barrel 53a, a second dehydration barrel 53b, and a third dehydration barrel 53c.

[0246] The drying barrel section 54 is composed of eight drying barrels, namely, a first drying barrel 54a, a second drying barrel 54b, a third drying barrel 54c, a fourth drying barrel 54d, a fifth drying barrel 54e, a sixth drying barrel 54f, a seventh drying barrel 54g, and an eighth drying barrel 54h.

[0247] In this manner, the barrel unit 51 is configured by connecting the divided 13 barrels 52a to 52b, 53a to 53c, and 54a to 54h from the upstream side to the downstream side.

[0248] The screw-type extruder 5 also has heating means (not shown) for individually heating each of the barrels 52a to 52b, 53a to 53c, and 54a to 54h to heat the water-containing crumbs in each of the barrels 52a to 52b, 53a to 53c, and 54a to 54h to a predetermined temperature. The number of heating means corresponds to each of the barrels 52a to 52b, 53a to 53c, and 54a to 54h. As such a heating means, for example, a configuration in which high-temperature steam is supplied from a steam supply means to a steam circulation jacket formed in each of the barrels 52a to 52b, 53a to 53c, and 54a to 54h is adopted, but is not limited thereto. The screw-type extruder 5 also has temperature control means (not shown) for controlling the set temperature of each heating means corresponding to each of the barrels 52a to 52b, 53a to 53c, and 54a to 54h.

[0249] The number of supply barrels, dewatering barrels, and drying barrels constituting each of barrel portions 52, 53, and 54 in barrel unit 51 is not limited to the embodiment shown in FIG. 2, and can be set to a number depending on factors such as the moisture content of the moisture-containing acrylic rubber crumbs to be dried.

[0250] For example, the number of supply barrels installed in supply barrel section 52 is, for example, 1 to 3. The number of dehydration barrels installed in dehydration barrel section 53 is, for example, preferably 2 to 10, and more preferably 3 to 6, since this allows efficient dehydration of the water-containing crumbs of sticky acrylic rubber. The number of drying barrels installed in drying barrel section 54 is, for example, preferably 2 to 10, and more preferably 3 to 8.

[0251] The pair of screws in the barrel unit 51 are rotated by a driving means such as a motor housed in the drive unit 50. The pair of screws extend from the upstream side to the downstream side in the barrel unit 51, and are rotated to convey the wet crumb supplied to the supply barrel section 52 to the downstream side while mixing them. The pair of screws is preferably a twin-shaft intermeshing type in which the peaks and valleys are intermeshed with each other, which can increase the dewatering and drying efficiency of the wet crumb.

[0252] The rotation directions of the pair of screws may be the same or different, but from the viewpoint of self-cleaning performance, it is preferable that the screws rotate in the same direction. The screw shape of the pair of screws is not particularly limited as long as it is a shape required for each of the barrel portions 52, 53, and 54.

[0253] The supply barrel section 52 is a region for supplying the wet crumbs into the barrel unit 51. The first supply barrel 52a of the supply barrel section 52 has a feed port 55 for supplying the wet crumbs into the barrel unit 51.

[0254] The dewatering barrel section 53 is a region where liquid (serum water) containing a coagulant and the like is separated from the water-containing crumbs and discharged.

[0255] The first to third dewatering barrels 53a to 53c constituting the dewatering barrel section 53 each have a dewatering slit 56a, 56b, 56c for discharging moisture from the wet crumb to the outside. A plurality of dewatering slits 56a, 56b, 56c are formed in each of the dewatering barrels 53a to 53c.

[0256] The slit width, i.e., mesh size, of each dewatering slit 56a, 56b, 56c may be appropriately selected depending on the conditions of use, and is typically 0.01 to 5 mm. From the viewpoints of minimizing loss of moist crumb and enabling efficient dewatering of the moist crumb, the width is preferably 0.1 to 1 mm, and more preferably 0.2 to 0.6 mm.

[0257] The removal of moisture from the wet crumb in each of the dehydration barrels 53a to 53c of the dehydration barrel section 53 can be done in two ways: in liquid form through the dehydration slits 56a, 56b, and 56c, and in vapor form. In the dehydration barrel section 53 of this embodiment, the removal of moisture in liquid form is defined as drainage, and the removal of moisture in vapor form is defined as exhaust steam, and are distinguished between these.

[0258] In the dehydration barrel section 53, the combination of drainage and exhaust steam is suitable because it can efficiently reduce the moisture content of the viscous acrylic rubber. In the dehydration barrel section 53, which of the first to third dehydration barrels 53a to 53c is used for drainage or steam exhaust may be appropriately set according to the purpose of use, but when the amount of ash in the acrylic rubber to be produced is usually reduced, it is preferable to increase the number of dehydration barrels for drainage. In that case, for example, as shown in FIG. 2, drainage is performed in the first and second dehydration barrels 53a and 53b on the upstream side, and steam exhaust is performed in the third dehydration barrel 53c on the downstream side. In addition, for example, when the dehydration barrel section 53 has four dehydration barrels, it is possible to consider an embodiment in which drainage is performed in three dehydration barrels on the upstream side and steam exhaust is performed in one dehydration barrel on the downstream side. On the other hand, when the moisture content is reduced, it is preferable to increase the number of dehydration barrels for steam exhaust.

[0259] As described above in the dehydrating / drying process, the set temperature of the dehydrating barrel section 53 is usually in the range of 60 to 150°C, preferably 70 to 140°C, and more preferably 80 to 130°C. The set temperature of the dehydrating barrel for dehydrating in a drainage state is usually in the range of 60 to 120°C, preferably 70 to 110°C, and more preferably 80 to 100°C. The set temperature of the dehydrating barrel for dehydrating in an exhaust steam state is usually in the range of 100 to 150°C, preferably 105 to 140°C, and more preferably 110 to 130°C.

[0260] The drying barrel section 54 is a region where the dehydrated water-containing crumbs are dried under reduced pressure. Among the first to eighth drying barrels 54a to 54h constituting the drying barrel section 54, the second drying barrel 54b, the fourth drying barrel 54d, the sixth drying barrel 54f and the eighth drying barrel 54h each have a vent port 58a, 58b, 58c, 58d for degassing. The vent ports 58a, 58b, 58c, 58d are each connected to a vent pipe (not shown).

[0261] A vacuum pump (not shown) is connected to the end of each vent pipe, and the pressure inside the drying barrel portion 54 is reduced to a predetermined level by operation of the vacuum pumps. The screw-type extruder 5 has a pressure control means (not shown) that controls the operation of the vacuum pumps to control the degree of reduced pressure inside the drying barrel portion 54.

[0262] The degree of reduced pressure in the drying barrel section 54 may be appropriately selected, but as described above, it is usually set to 1 to 50 kPa, preferably 2 to 30 kPa, and more preferably 3 to 20 kPa.

[0263] The temperature set within the drying barrel section 54 may be appropriately selected, but as described above, it is usually set to 100 to 250°C, preferably 110 to 200°C, and more preferably 120 to 180°C.

[0264] In each of the drying barrels 54a to 54h that make up the drying barrel section 54, the set temperatures in all of the drying barrels 54a to 54h may be similar or different, but it is preferable to set the temperature on the downstream side (die 59 side) higher than the temperature on the upstream side (dehydration barrel section 53 side), as this improves drying efficiency.

[0265] The die 59 is a metal mold disposed at the downstream end of the barrel unit 51, and has an outlet of a predetermined nozzle shape. The acrylic rubber dried in the drying barrel section 54 passes through the outlet of the die 59, and is extruded into a shape corresponding to the predetermined nozzle shape. The acrylic rubber passing through the die 59 is molded into various shapes, such as granular, columnar, round rod, and sheet, depending on the nozzle shape of the die 59. For example, the acrylic rubber can be extruded into a sheet by forming the outlet of the die 59 into a substantially rectangular shape. A breaker plate or a wire mesh may or may not be provided between the screw and the die 59.

[0266] According to the screw-type extruder 5 of this embodiment, the water-containing crumbs of the raw acrylic rubber are extruded into a sheet-like dry rubber in the following manner.

[0267] The hydrous crumbs of the acrylic rubber obtained through the washing process are supplied to the supply barrel section 52 from the feed port 55. The hydrous crumbs supplied to the supply barrel section 52 are transferred from the supply barrel section 52 to the dehydration barrel section 53 by the rotation of the pair of screws in the barrel unit 51. In the dehydration barrel section 53, the hydrous crumbs are dehydrated by draining water contained in the hydrous crumbs and discharging steam from the dehydration slits 56a, 56b, and 56c provided in the first to third dehydration barrels 53a to 53c, respectively, as described above.

[0268] The water-containing crumbs dewatered in the dewatering barrel section 53 are sent to the drying barrel section 54 by the rotation of a pair of screws in the barrel unit 51. The water-containing crumbs sent to the drying barrel section 54 are plasticized and mixed to become a melt, and are transported downstream while generating heat and increasing in temperature. Then, the water contained in the acrylic rubber melt vaporizes, and the water (steam) is discharged to the outside through vent pipes (not shown) connected to each of the vent ports 58a, 58b, 58c, and 58d.

[0269] As described above, by passing through the drying barrel section 54, the water-containing crumb is dried and becomes a molten acrylic rubber. The acrylic rubber is supplied to the die 59 by the rotation of the pair of screws in the barrel unit 51 and is extruded from the die 59 as a sheet-like dried rubber.

[0270] Here, an example of operating conditions for the screw-type extruder 5 according to this embodiment will be given.

[0271] The rotation speed (N) of the pair of screws in barrel unit 51 may be appropriately selected depending on various conditions, and is usually set to 10 to 1,000 rpm. From the viewpoint of efficiently reducing the water content and gel amount in the acrylic rubber veil, it is preferably 50 to 750 rpm, more preferably 100 to 500 rpm, and most preferably 120 to 300 rpm.

[0272] The extrusion rate (Q) of the acrylic rubber is not particularly limited, but is usually 100 to 1,500 kg / hr, preferably 300 to 1,200 kg / hr, more preferably 400 to 1,000 kg / hr, and most preferably 500 to 800 kg / hr.

[0273] In addition, the ratio (Q / N) of the extrusion amount (Q) of the acrylic rubber to the screw rotation speed (N) is not particularly limited, but is usually 1 to 20, preferably 2 to 10, more preferably 3 to 8, and particularly preferably 4 to 6.

[0274] The cooling device 6 shown in Fig. 1 is configured to cool the dried rubber obtained through the dehydration process using a dehydrator and the drying process using a dryer. As a cooling method using the cooling device 6, various methods can be adopted, including an air-cooling method using blowing air or air conditioning, a water-spraying method in which water is sprayed, and an immersion method in which the rubber is immersed in water. The dried rubber may also be cooled by leaving it at room temperature.

[0275] As described above, the dry rubber discharged from the screw-type extruder 5 is extruded and molded into various shapes such as granules, columns, round rods, sheets, etc., depending on the nozzle shape of the die 59. Hereinafter, a conveying type cooling device 60 that cools the sheet-shaped dry rubber 10 molded into a sheet will be described as an example of the cooling device 6 with reference to Fig. 3.

[0276] Fig. 3 shows the configuration of a conveyor-type cooling device 60 suitable for use as the cooling device 6 shown in Fig. 1. The conveyor-type cooling device 60 shown in Fig. 3 is configured to cool the sheet-like dry rubber 10 discharged from the discharge port of the die 59 of the screw-type extruder 5 by air cooling while conveying the sheet-like dry rubber 10. By using this conveyor-type cooling device 60, the sheet-like dry rubber discharged from the screw-type extruder 5 can be suitably cooled.

[0277] The conveying cooling device 60 shown in FIG. 3 is used by being directly connected to the die 59 of the screw-type extruder 5 shown in FIG.

[0278] The conveying type cooling device 60 has a conveyor 61 that conveys the sheet-like dried rubber 10 discharged from the die 59 of the screw-type extruder 5 in the direction of arrow A in Figure 3, and a cooling means 65 that blows cold air onto the sheet-like dried rubber 10 on the conveyor 61.

[0279] The conveyor 61 has rollers 62, 63, and a conveyor belt 64 that is wound around the rollers 62, 63 and on which the sheet-like dry rubber 10 is placed. The conveyor 61 is configured to continuously transport the sheet-like dry rubber 10 discharged from the die 59 of the screw-type extruder 5 onto the conveyor belt 64 downstream (to the right in FIG. 3).

[0280] The cooling means 65 is not particularly limited, but may be, for example, a means configured to blow cooling air sent from a cooling air generating means (not shown) onto the surface of the sheet-like dried rubber 10 on the conveyor belt 64.

[0281] The length L1 of the conveyor 61 and the cooling means 65 of the transport-type cooling device 60 (the length of the part where cooling air can be blown) is not particularly limited, but is, for example, 10 to 100 m, and preferably 20 to 50 m. The transport speed of the sheet-like dry rubber 10 in the transport-type cooling device 60 may be appropriately adjusted depending on the length L1 of the conveyor 61 and the cooling means 65, the discharge speed of the sheet-like dry rubber 10 discharged from the die 59 of the screw-type extruder 5, the target cooling speed and cooling time, and is, for example, 10 to 100 m / hr, and more preferably 15 to 70 m / hr.

[0282] According to the conveying type cooling device 60 shown in Figure 3, the sheet-like dry rubber 10 discharged from the die 59 of the screw-type extruder 5 is conveyed by a conveyor 61 while cooling air is blown from a cooling means 65 onto the sheet-like dry rubber 10, thereby cooling the sheet-like dry rubber 10.

[0283] 3, the transportable cooling device 60 is not particularly limited to a configuration including one conveyor 61 and one cooling means 65, but may be configured to include two or more conveyors 61 and two or more corresponding cooling means 65. In that case, the total length of each of the two or more conveyors 61 and the cooling means 65 may be within the above range.

[0284] The baling device 7 shown in Fig. 1 is configured to process the dry rubber extruded from the screw-type extruder 5 and cooled in the cooling device 6 to produce a bale, which is a block. As described above, the screw-type extruder 5 is capable of extruding the dry rubber into various shapes such as granules, columns, round bars, and sheets, and the baling device 7 is configured to bales the dry rubber thus formed into various shapes. The weight and shape of the acrylic rubber bales produced by the baling device 7 are not particularly limited, but for example, an approximately rectangular parallelepiped acrylic rubber bale weighing about 20 kg is produced.

[0285] The baling device 7 may include, for example, a baler, and the cooled, dried rubber may be compressed by the baler to produce an acrylic rubber bale.

[0286] Furthermore, when the sheet-like dry rubber 10 is produced by the screw-type extruder 5, an acrylic rubber bale in which the sheet-like dry rubber 10 is laminated may be produced. For example, a cutting mechanism for cutting the sheet-like dry rubber 10 may be provided in the baling device 7 arranged downstream of the conveying cooling device 60 shown in FIG. 3. Specifically, the cutting mechanism of the baling device 7 is configured, for example, to continuously cut the cooled sheet-like dry rubber 10 at predetermined intervals and process it into cut sheet-like dry rubber 16 of a predetermined size. By laminating a plurality of cut sheet-like dry rubber 16 cut to a predetermined size by the cutting mechanism, an acrylic rubber bale in which the cut sheet-like dry rubber 16 is laminated can be produced.

[0287] When manufacturing an acrylic rubber veil in which cut sheet-like dry rubber 16 is laminated, it is preferable to laminate cut sheet-like dry rubber 16 at, for example, 40° C. or higher. By laminating cut sheet-like dry rubber 16 at 40° C. or higher, good air release is achieved by further cooling and compression due to its own weight. EXAMPLES

[0288] The present invention will be described in more detail below with reference to examples and comparative examples. In each example, "parts", "%" and "ratio" are by weight unless otherwise specified. Various physical properties were evaluated according to the following methods.

[0289] [Monomer composition] Regarding the monomer composition of the acrylic rubber, the monomer composition of each monomer unit in the acrylic rubber was confirmed by H-NMR, and the remaining activity of the reactive groups in the acrylic rubber and the content of each reactive group were confirmed by the following test method. The content ratio of each monomer unit in the acrylic rubber was calculated from the amount of each monomer used in the polymerization reaction and the polymerization conversion rate. Specifically, the polymerization reaction was an emulsion polymerization reaction, and the polymerization conversion rate was approximately 100%, with no unreacted monomers being confirmed, so the content ratio of each monomer unit was set to be the same as the amount of each monomer used.

[0290] (Reactive group content) The content of reactive groups in the acrylic rubber veil was measured by the following method. (1) The amount of carboxyl groups was calculated by dissolving the acrylic rubber veil in acetone and performing potentiometric titration with potassium hydroxide solution. (2) The amount of epoxy groups was calculated by dissolving the acrylic rubber base in methyl ethyl ketone, adding a specified amount of hydrochloric acid to react with the epoxy groups, and titrating the amount of residual hydrochloric acid with potassium hydroxide. (3) The amount of chlorine was calculated by completely burning an acrylic rubber veil in a combustion flask, absorbing the chlorine generated in water, and titrating it with silver nitrate.

[0291] [Ash content] The ash content (%) in the acrylic rubber veil was measured in accordance with JIS K6228 Method A.

[0292] [Ash content] The amount (ppm) of each component in the acrylic rubber veil ash was measured by pressing the ash sampled after the above-mentioned ash content measurement onto a titration filter paper of Φ20 mm and subjecting it to XRF measurement using ZSX Primus (manufactured by Rigaku Co., Ltd.).

[0293] [Gel amount] The gel content (%) of the acrylic rubber veil is the amount of insoluble matter in methyl ethyl ketone, and was determined by the following method. Approximately 0.2 g of acrylic rubber bale was weighed out (Xg), immersed in 100 ml of methyl ethyl ketone and left to stand at room temperature for 24 hours, after which the insoluble matter in methyl ethyl ketone was filtered off using an 80 mesh wire screen. The filtrate, i.e., the filtrate containing only the rubber components soluble in methyl ethyl ketone, was evaporated, dried and solidified, and the dried solid content (Yg) was weighed and calculated using the following formula. Gel volume (%) = 100 × (XY) / X

[0294] [specific gravity] The specific gravity of the acrylic rubber veil was measured in accordance with JIS K6268 Crosslinked Rubber - Density Measurement Method A.

[0295] [Glass transition temperature (Tg)] The glass transition temperature (Tg) of the acrylic rubber was measured using a differential scanning calorimeter (DSC, product name "X-DSC7000", manufactured by Hitachi High-Tech Science Corporation).

[0296] [pH] The pH of the acrylic rubber veil was measured with a pH electrode after dissolving 6 g (±0.05 g) of acrylic rubber in 100 g of tetrahydrofuran, adding 2.0 ml of distilled water, and confirming complete dissolution.

[0297] [Water content] The water content (%) of the acrylic rubber veil was measured in accordance with JIS K6238-1: Oven A (volatile matter measurement) method.

[0298] [Molecular weight and molecular weight distribution] The weight average molecular weight (Mw) and molecular weight distribution (Mz / Mw) of acrylic rubber are absolute molecular weight and absolute molecular weight distribution measured by GPC-MALS method using a solution of dimethylformamide with 0.05 mol / L lithium chloride and 0.01% 37% concentrated hydrochloric acid as a solvent. Specifically, a multi-angle laser light scattering photometer (MALS) and a differential refractometer (RI) were incorporated into a GPC (Gel Permeation Chromatography) device, and the light scattering intensity and refractive index difference of the molecular chain solution size-fractionated by the GPC device were measured over the elution time, and the molecular weight of the solute and its content were calculated sequentially. The measurement conditions and method using the GPC device are as follows. Column: 2 TSKgel α-M (φ7.8mm×30cm, Tosoh Corporation) Column temperature: 40℃ Flow rate: 0.8ml / mm Sample preparation: 5 ml of solvent was added to 10 mg of sample, and the mixture was gently stirred at room temperature (dissolution was visually confirmed).Then, the mixture was filtered using a 0.5 μm filter.

[0299] [Complex viscosity] The complex viscosity η of the acrylic rubber veil was measured at 473% strain and 1 Hz using a dynamic viscoelasticity measuring device "Rubber Process Analyzer RPA-2000" (manufactured by Alpha Technology Co., Ltd.) to measure the temperature dispersion (40 to 120°C) and obtain the complex viscosity η at each temperature. Here, the dynamic viscoelasticity at 60°C of the above-mentioned dynamic viscoelasticity was taken as the complex viscosity η(60°C), and the dynamic viscoelasticity at 100°C was taken as the complex viscosity η(100°C), and the values ​​of η(100°C) / η(60°C) and η(60°C) / η(100°C) were calculated.

[0300] [Mooney viscosity (ML1+4, 100℃)] The Mooney viscosity (ML1+4,100°C) of the acrylic rubber veil was measured in accordance with the physical testing method for uncrosslinked rubber of JIS K6300.

[0301] [Processability evaluation] The processability of the rubber samples was evaluated by putting the rubber samples into a Banbury mixer heated to 50°C and masticating for 1 minute, then adding compounding ingredient A of the rubber mixture formulation shown in Table 1, and measuring the time until the rubber mixture in the first stage was integrated and showed the maximum torque value, i.e., BIT (Black Incorporation Time), and evaluating it with an index of 100 for Comparative Example 1 (the smaller the index, the better the processability).

[0302] [Water resistance evaluation] The water resistance of the rubber samples was evaluated by an immersion test in accordance with JIS K6258, in which the crosslinked rubber samples were immersed in distilled water at 85°C for 100 hours, and the volume change rate before and after immersion was calculated according to the following formula, with Comparative Example 1 being set at 100 (the smaller the index, the better the water resistance). Volume change rate before and after immersion (%) = (volume of test piece after immersion - volume of test piece before immersion) / volume of test piece before immersion) x 100

[0303] [Example 1] A mixing vessel equipped with a homomixer was charged with 46 parts of pure water, 48.5 parts of ethyl acrylate, 29 parts of n-butyl acrylate, 21 parts of methoxyethyl acrylate, 1.5 parts of vinyl chloroacetate, and, as emulsifiers, 0.709 parts of sodium lauryl sulfate and 1.82 parts of polyoxyethylene dodecyl ether (molecular weight 1500), and the mixture was stirred to obtain a monomer emulsion.

[0304] Next, 170 parts of pure water and 3 parts of the monomer emulsion obtained by emulsion polymerization were added to a polymerization reaction tank equipped with a thermometer and a stirrer, and cooled to 12°C under a nitrogen stream. Then, the remainder of the monomer emulsion, 0.00033 parts of ferrous sulfate, 0.264 parts of sodium ascorbate, and 0.22 parts of potassium persulfate were continuously dropped into the polymerization reaction tank over 3 hours. Thereafter, the reaction was continued while maintaining the temperature in the polymerization reaction tank at 23°C, and it was confirmed that the polymerization conversion rate reached approximately 100%, and hydroquinone was added as a polymerization terminator to terminate the polymerization reaction, thereby obtaining an emulsion polymerization liquid.

[0305] In a coagulation bath equipped with a thermometer and agitator, the emulsion polymerization liquid obtained above was heated to 80°C and continuously added to a 2% aqueous sodium sulfate solution (coagulation liquid) that had been heated to 80°C and vigorously stirred (600 rpm: peripheral speed 3.1 m / s), to coagulate the polymer, which was then filtered off to obtain hydrous crumbs.

[0306] Next, 194 parts of hot water (70°C) was added to the coagulation bath and stirred for 15 minutes, after which the water was removed, and 194 parts of hot water (70°C) was added again and stirred for 15 minutes to wash the wet crumbs. The washed wet crumbs (wet crumb temperature 65°C) were fed to a screw-type extruder, dehydrated and dried, and extruded into a sheet-like dry rubber with a width of 300 mm and a thickness of 10 mm. Furthermore, the sheet-like dry rubber was cooled at a cooling rate of 200°C / hr using a conveying cooling device directly connected to the screw-type extruder.

[0307] The screw extruder used in this Example 1 is composed of one supply barrel, three dehydration barrels (first to third dehydration barrels), and five drying barrels (first to fifth drying barrels). The first and second dehydration barrels discharge water, and the third dehydration barrel discharges steam. The operating conditions of the screw extruder were as follows.

[0308] Water content: Moisture content of wet crumbs after draining in the second dewatering barrel: 20% Moisture content of wet crumb after steaming in the third dewatering barrel is 10% Moisture content of wet crumb after drying in the fifth drying barrel: 0.4% Rubber Temperature: Temperature of wet crumbs fed into the first feed barrel: 65℃ -Temperature of rubber discharged from screw extruder: 140℃ Dehydration barrel temperature setting: First dehydration barrel: 90℃ Second dehydration barrel: 100℃ ·Third dehydration barrel: 120℃ ·First drying barrel: 120℃ Second drying barrel: 130℃ ·Third drying barrel: 140℃ ·Fourth drying barrel: 160℃ · Fifth drying barrel: 180℃ Operating conditions: Diameter of the screw in the barrel unit (D): 132mm Total length of the screw in the barrel unit (L): 4620mm Length / Depth:35 - Rotation speed of the screw in the barrel unit: 135 rpm -Rubber extrusion rate from die: 700kg / hr Die resin pressure: 2MPa

[0309] The extruded sheet-like dried rubber was cooled to 50°C, cut with a cutter, and laminated to 20 parts (20 kg) before the temperature dropped below 40°C to obtain an acrylic rubber veil (A). The reactive group content, ash content, ash component content, specific gravity, gel content, glass transition temperature (Tg), pH, water content, molecular weight, molecular weight distribution, complex viscosity, and Mooney viscosity (ML1+4,100°C) of the obtained acrylic rubber veil (A) were measured and are shown in Table 2. The value of "water content after dehydration (drainage) (%)" shown in the dehydration process column in Table 2 is the water content of the water-containing crumb immediately after drainage in the drainage type dehydration barrel (immediately before the exhaust steam type dehydration barrel).

[0310] Next, 100 parts of the acrylic rubber veil (A) and compounding ingredient A of "Compound 1" shown in Table 1 were added using a Banbury mixer and mixed for 5 minutes at 50°C. At this time, the processability of the acrylic rubber veil was evaluated, and the results are shown in Table 2. Furthermore, the resulting mixture was transferred to a roll at 50°C, and compounding ingredient B of "Compound 1" was compounded and mixed to obtain a rubber mixture.

[0311] [Table 1]

[0312] The obtained rubber mixture was placed in a mold 15 cm long, 15 cm wide, and 0.2 cm deep, and pressed at 180°C for 10 minutes while applying a pressure of 10 MPa to cause primary crosslinking, and then the obtained primary crosslinked product was further heated in a gear oven at 180°C for 2 hours to cause secondary crosslinking, thereby obtaining a sheet-like crosslinked rubber product. A test piece measuring 3 cm x 2 cm x 0.2 cm was cut from the obtained sheet-like crosslinked rubber product and subjected to a water resistance test, and the results are shown in Table 2.

[0313] [Example 2] The monomer components were changed to 98.5 parts of ethyl acrylate and 1.5 parts of vinyl chloroacetate, the temperature of the first dehydration barrel of the screw extruder was changed to 100°C, the temperature of the second dehydration barrel was changed to 120°C, and only the first dehydration barrel was used for drainage. In addition, the moisture content of the water-containing crumb after drainage in the first dehydration barrel was changed to 30%. The same procedure as in Example 1 was carried out, and an acrylic rubber veil (B) was obtained and its properties were evaluated. The results are shown in Table 2. [Example 3]

[0314] The same procedure as in Example 2 was carried out except that the monomer components were changed to 43 parts of ethyl acrylate, 25 parts of n-butyl acrylate, 26 parts of methoxyethyl acrylate, 2 parts of acrylonitrile, and 4 parts of allyl glycidyl ether, and an acrylic rubber veil (C) was obtained and its properties were evaluated (the compounding agent was replaced with "Compound 2"). The results are shown in Table 2.

[0315] [Example 4] The same procedure as in Example 2 was carried out except that the monomer components were changed to 4.5 parts of ethyl acrylate, 64.5 parts of n-butyl acrylate, 39.5 parts of methoxyethyl acrylate, and 1.5 parts of mono n-butyl fumarate, and an acrylic rubber veil (D) was obtained and its properties were evaluated (the compounding agent was changed to "Compound 3"). The results are shown in Table 2.

[0316] [Example 5] The same procedure as in Example 2 was carried out except that the monomer components were changed to 42.2 parts of ethyl acrylate, 35 parts of n-butyl acrylate, 20 parts of methoxyethyl acrylate, 1.5 parts of acrylonitrile, and 1.3 parts of vinyl chloroacetate, to obtain an acrylic rubber veil (E), and the properties thereof were evaluated. The results are shown in Table 2.

[0317] [Comparative Example 1] A 0.7% aqueous sodium sulfate solution was added directly to the emulsion polymerization liquid (rotation speed 100 rpm, peripheral speed 0.5 m / s) subjected to emulsion polymerization in the same manner as in Example 5 to generate hydrous crumbs, 194 parts of industrial water were added to 100 parts of the generated hydrous crumbs, and the mixture was stirred in a coagulation tank at 25°C for 5 minutes, after which the hydrous crumbs were washed 4 times by draining the water from the coagulation tank, and then 194 parts of an aqueous sulfuric acid solution of pH 3 was added and stirred at 25°C for 5 minutes, after which the water was drained from the coagulation tank and acid washed once, 194 parts of pure water was added and pure water washed once, and then the mixture was dried in a hot air dryer at 160°C to obtain an acrylic rubber (F) with a water content of 0.4% by weight. The properties of the obtained crumb-like acrylic rubber (F) were evaluated and shown in Table 2.

[0318] [Reference example 1] The washing process was carried out in the same manner as in Example 5, and the washed water-containing crumbs were dried in a hot air dryer at 160° C. to obtain an acrylic rubber (G) with a water content of 0.4% by weight. The properties of the obtained crumb-like acrylic rubber (G) were evaluated and are shown in Table 2.

[0319] [Table 2]

[0320] From Table 2, it can be seen that the acrylic rubber veils (A) to (E) which contain the (meth)acrylic acid ester of the present invention as a main component, have an ash content of 0.3% by weight or less, and the content of at least one element selected from sodium, sulfur, calcium, magnesium and phosphorus in the ash is 50% by weight or more in total, and have a gel content of 50% by weight or less of methyl ethyl ketone insoluble matter, are remarkably excellent in processability and water resistance (comparison between Examples 1 to 5 and Comparative Example 1).

[0321] Furthermore, Table 2 shows that when a coagulation liquid is added to an emulsion polymerization liquid in the coagulation reaction to generate hydrous crumbs, the ash content does not decrease and the water resistance of the acrylic rubber veil is insufficient, even if the washing process involves four water washes, one acid wash, and one pure water wash (Comparative Example 1).On the other hand, when a coagulation reaction involves adding an emulsion polymerization liquid to a high-concentration coagulation liquid that is being vigorously stirred to generate hydrous crumbs, the ash content decreases and water resistance improves simply by washing twice with warm water (Reference Example 1).

[0322] In addition, looking at the relationship between the amount of sodium (Na) and the amount of sulfur (S) in the ash in Table 2, it can be seen that by carrying out the coagulation method and washing method in Reference Example 1, the total amount of sodium (Na) and sulfur (S) (Na+S) remains the same as in Comparative Example 1, but the amount of sodium (Na) is reduced and the Na / S ratio is smaller. This is because by carrying out the coagulation and washing method in Reference Example 1, most of the coagulant (sodium sulfate: Na2SO4: high Na ratio) used is removed, but the emulsifier (sodium lauryl sulfate: NaC 12 H 25 It is presumed that this is because sodium (Na) and sulfur (S) derived from sulfur dioxide (SO4) are inherent in the hydrous crumbs and cannot be fully removed by washing.

[0323] Also, from Table 2, it is seen that the method of Reference Example 1 can improve water resistance, but hardly improves processability.

[0324] In contrast, by carrying out a coagulation reaction in the same manner as in Reference Example 1, washing twice with warm water, and then dehydrating and drying using a screw-type extruder until the water content was less than 1% by weight, it is clear that the ash content and the gel content of methyl ethyl ketone insoluble matter in the acrylic rubber bales of Examples 1 to 5 were significantly reduced, and the water resistance and processability of the acrylic rubber bales were significantly improved (comparison of Examples 1 to 5 with Comparative Example 1 and Reference Example 1). [Explanation of symbols]

[0325] 1 Acrylic rubber manufacturing system 3 Coagulation device 4. Cleaning equipment 5 screw extruder 6 Cooling device 7 Baling Equipment

Claims

1. An acrylic rubber veil having a rectangular parallelepiped shape, which is composed of an acrylic rubber obtained by emulsion polymerization, the main constituent unit of which is a group derived from a (meth)acrylic acid ester, and which contains constituent units having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group, the acrylic rubber having an ash content of 0.0001 to 0.25% by weight as measured by JIS K6288 Method A, the ash containing at least one element selected from the group consisting of sodium, sulfur, calcium, magnesium, and phosphorus being 50% by weight or more in total relative to the total ash content, and the acrylic rubber having a gel content of methyl ethyl ketone insolubles being 10% by weight or less.

2. 2. The acrylic rubber veil according to claim 1, having an ash content of 0.2% by weight or less.

3. 3. The acrylic rubber veil according to claim 1 or 2, wherein the ash contains sodium and sulfur.

4. The acrylic rubber veil according to any one of claims 1 to 3, wherein the reactive group content of the acrylic rubber is 0.001 to 5% by weight.

5. The acrylic rubber veil according to any one of claims 1 to 4, wherein the weight average molecular weight (Mw) of the acrylic rubber is in the range of 1,000,000 to 5,000,000.

6. 6. The acrylic rubber veil according to any one of claims 1 to 5, wherein the amount of gel insoluble in methyl ethyl ketone is 5% by weight or less.

7. 7. The acrylic rubber veil according to claim 1, wherein the amount of gel insoluble in methyl ethyl ketone is 3.4% by weight or less.

8. 8. The acrylic rubber veil according to claim 1, wherein the total amount of sodium and sulfur in the ash is 80% by weight or more based on the total ash content.

9. 9. The acrylic rubber veil according to any one of claims 1 to 8, wherein the ratio of sodium to sulfur in the ash ([Na] / [S]) is in the range of 0.75 to 0.95 by weight.

10. The acrylic rubber veil according to any one of claims 1 to 9, which has a pH of 2 to 6.

11. The acrylic rubber veil according to any one of claims 1 to 10, wherein the complex viscosity at 100°C ([η]100°C) is 1,500 to 6,000 Pa·s, and the ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is 0.5 to 0.

99. (Here, the complex viscosity is measured by measuring temperature dispersion (40 to 120°C) at 473% strain and 1 Hz using a dynamic viscoelasticity measuring device "Rubber Process Analyzer RPA-2000" (manufactured by Alpha Technology Co., Ltd.), determining the complex viscosity η at each temperature, and among the above-mentioned dynamic viscoelasticity, the dynamic viscoelasticity at 60°C is defined as the complex viscosity [η]60°C, and the dynamic viscoelasticity at 100°C is defined as the complex viscosity [η]100°C.)

12. 12. The acrylic rubber veil according to claim 11, wherein the ratio ([η]100°C / [η]60°C) of the complex viscosity at 100°C ([η]100°C) to the complex viscosity at 60°C ([η]60°C) is 0.83 or more.

13. The acrylic rubber veil according to any one of claims 1 to 12, which has a specific gravity in the range of 0.7 to 1.5 as measured in accordance with JIS K6268, Crosslinked Rubber - Density Measurement Method A.

14. The acrylic rubber veil according to any one of claims 1 to 13, having a water content of less than 1% by weight.

15. an emulsion polymerization step of emulsifying a monomer component mainly composed of a (meth)acrylic acid ester and a monomer component having at least one reactive group selected from the group consisting of a carboxyl group, an epoxy group, and a halogen group, with water and an emulsifier, and emulsion-polymerizing the resulting emulsion in the presence of a polymerization catalyst to obtain an emulsion polymerization liquid; a coagulation step in which the obtained emulsion polymerization liquid is added to a stirred aqueous solution containing a coagulant to produce water-containing crumbs; A washing step of washing the generated hydrous crumbs with warm water of 40°C or higher; A drying step in which the washed wet crumb is dehydrated and dried using a screw-type extruder, and extruded as a dry rubber dried to a moisture content of less than 1% by weight; a baling process in which the extruded dry rubber is shaped into rectangular bales; A method for producing an acrylic rubber veil comprising the steps of:

16. The method for producing an acrylic rubber veil according to claim 15, which produces the acrylic rubber veil according to any one of claims 1 to 14.

17. 17. The method for producing an acrylic rubber veil according to claim 15 or 16, wherein the emulsifier contains at least one element selected from the group consisting of sodium, sulfur and phosphorus, and / or the coagulant contains at least one element selected from the group consisting of sodium, sulfur, calcium and magnesium.

18. The method for producing an acrylic rubber veil according to any one of claims 15 to 17, wherein the polymerization conversion rate of the emulsion polymerization is 90% by weight or more.

19. The method for producing an acrylic rubber veil according to any one of claims 15 to 18, wherein the temperature of the water-containing crumb fed into the screw-type extruder is 40 to 100°C.

20. The method for producing an acrylic rubber veil according to any one of claims 15 to 19, further comprising a dehydration step of squeezing out water from the water-containing crumb.

21. The method for producing an acrylic rubber veil according to claim 20, wherein the hydrous crumb is dehydrated to a moisture content of 1 to 40% by weight.

22. The method for producing an acrylic rubber veil according to claim 21, wherein the water content after dehydration is in the range of 5 to 35% by weight.

23. The method for producing an acrylic rubber veil according to any one of claims 15 to 22, wherein the degree of vacuum in the drying barrel of the screw-type extruder is in the range of 1 to 50 kPa, and the drying temperature is in the range of 100 to 250°C.

24. The method for producing an acrylic rubber veil according to any one of claims 15 to 23, wherein the moisture content of the moisture-containing crumb at the die portion of the screw-type extruder is less than 1% by weight.

25. The method for producing an acrylic rubber veil according to any one of claims 15 to 24, wherein the resin pressure at the die portion of the screw-type extruder is in the range of 0.1 to 10 MPa.

26. The method for producing an acrylic rubber veil according to any one of claims 15 to 25, wherein the ratio (Q / N) of the extrusion rate (Q) to the rotation speed (N) of the screw-type extruder is in the range of 2 to 10.

27. The method for producing an acrylic rubber veil according to any one of claims 15 to 26, wherein the dried rubber is in the form of a sheet.

28. A rubber mixture obtained by mixing the acrylic rubber veil according to any one of claims 1 to 14 with a filler and a crosslinking agent.

29. 29. A rubber mixture according to claim 28, wherein the filler is a reinforcing filler.

30. 29. The rubber mixture of claim 28, wherein the filler is carbon black.

31. 29. A rubber mix according to claim 28, wherein the filler is silica.

32. 32. A rubber mixture according to claim 28, wherein the crosslinking agent is a polyamine compound, an ammonium carboxylate, a metal dithiocarbamate or a triazine thiol compound.

33. The rubber mixture according to any one of claims 28 to 32, further comprising an antioxidant.

34. 34. The rubber mixture of claim 33, wherein the antioxidant is an amine-based antioxidant.

35. A method for producing a rubber mixture, comprising mixing the acrylic rubber veil according to any one of claims 1 to 14 with a filler, a crosslinking agent and, if necessary, an antioxidant in a mixer.

36. A method for producing a rubber mixture, comprising mixing the acrylic rubber veil according to any one of claims 1 to 14, a filler, and, if necessary, an antioxidant, and then mixing a crosslinking agent.

37. A cross-linked rubber product obtained by cross-linking the rubber mixture according to any one of claims 28 to 34.

38. The cross-linked rubber product according to claim 37, wherein the cross-linking is a primary cross-linking and a secondary cross-linking.

39. A method for producing a cross-linked rubber product, which comprises subjecting the rubber mixture according to any one of claims 28 to 34 to a primary cross-link and then a secondary cross-linking.

Citation Information

Patent Citations

  • Driving method for rubber-like polymer

    JP1989225512A

  • Continuous production of acrylic rubber

    JP1994279507A

  • Manufacturing process of thermoplastic elastomer composition

    JP2005306948A

  • Manufacturing method of rubbery polymer

    JP2006328239A

  • ACRYLIC RUBBER COMPOSITION AND METHOD FOR MANUFACTURING ACRYLIC RUBBER

    JP3599962B2